Earliest fossil record of pollen-foraging megachiline bees - Christian Geier; Michael S. Engel; André Nel; Johannes M. Bouchal; Silvia Ulrich; Gabrielle Gourdet; Valérie Ngô Muller; Friðgeir Grímsson (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The impact of non-native trees on galling and herbivory in New York City across space and time - Liam D. Engel; Adanna Smith; Irma Cardenas; Dunya Abdulkarem; Claudia C. Vasquez; Evon Hekkala; Emily M. Herstoff; Michael Tessler (Oecologia, 2026)
Cities and suburbs frequently plant native and non-native trees as foundation species, with non-natives cultivated in these areas for centuries while remaining non-invasive. Although previous research has found that native trees often host more arthropods, studies have not simultaneously looked across space and time to determine the consistency of tree origin on urban arthropods. We combined varied methods across spatial and temporal scales in New York City to test if native tree leaves consistently have more insect and mite interactions than long-established non-native trees, predicting stronger effect sizes for specialists (galling arthropods) than generalists (herbivory). We examined (1) congeneric species pairs, controlled for growing conditions and stoichiometry in an arboretum, (2) diverse oaks at a botanical garden, (3) community science records across Brooklyn, and (4) herbarium specimens from 1883 through present across the city. Across spatiotemporal scales, we found consistent results. Specialist interactions were striking: contemporary native trees supported numerous galling species, while only one congeneric non-native species hosted any galls. For generalists, contemporary native trees had equivalent to slightly greater herbivory. Over the last century, herbarium records showed that herbivory increased on non-native trees to nearly the level of natives, whereas native trees increased in gall abundance while non-native trees remained rarely galled. Our results demonstrate the impact of tree origin on tree-arthropod interactions in a real-world urban setting, with far fewer galls even when non-native tree species have been cultivated locally for centuries. Our findings will help city planners and property owners confidently choose native trees to promote arthropod biodiversity.

Biomass increments of Prunus serotina Ehrh. in central European temperate forests - Mateusz Muzolf; Sebastian Bury; Markus Engel; Anne Strieder; Oliver Eglin; Andrzej M. Jagodziński; Marcin K. Dyderski (Forest Ecology and Management, 2026)

Palaeoecological potential of chironomid (non-biting midge) remains encountered on pollen slides - S. Engels; O. Heiri; J. Hinkelman; M. Jambrović (Review of Palaeobotany and Palynology, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Granulated bovine oocytes represent a lipid rich phenotype with enhanced developmental competence - Rebecca Herbicht; Kathrin M. Engel; Lars Teschke; Falk Butter; Thomas Fröhlich; Claudia Klein (Animal Reproduction Science, 2026)

Mitral annular plane systolic excursion to left atrial volume ratio as a novel index to assess ventricular filling pressure in dogs with myxomatous mitral valve disease - Jeff M. Perez; Jorge Isidoro Matos; Oscar Monge-Utrilla; Pablo Fernandez-Rodriguez; Soraya Falcon-Cordon; Javier Engel-Manchado (Veterinary Research Communications, 2026)

Longer-term neurological and endocrine/metabolic conditions in the deepwater horizon oil spill coast guard cohort study: A principal component analysis - Hristina Denic-Roberts; Jordan McAdam; Lawrence S. Engel; Jeanine M. Buchanich; Rachel G. Miller; Evelyn O. Talbott; Dana L. Thomas; Glen A. Cook; Blake Hansen; Jill E. Emerick; Tina Costacou; Jennifer A. Rusiecki (International Archives of Occupational and Environmental Health, 2026)
Purpose Deepwater Horizon oil spill (DWHOS) responders potentially experienced multiple stressors. We examined associations between DWHOS deployment-related stressor patterns and neurological and endocrine/metabolic conditions among U.S. Coast Guard active duty responders who completed post-deployment surveys (n = 3102). Methods Deployment-related stressor patterns were identified using principal component analysis of self-reported stressors. Neurological and endocrine/metabolic outcomes were classified from military health encounter records. Associations between principal components (PCs) and incident outcomes (2010–2015) were estimated through Cox proportional hazards regression. Results A five-component solution explained 79.2% of the variance. PC1 (high physical/moderate chemical stressor pattern) was associated with migraine [adjusted hazard ratio (aHR): 1.25, 95% confidence interval (CI): 1.01–1.56]. PC2 (high crude oil/dispersant stressor pattern) was associated with several migraine/headache conditions including migraine with aura (1.54, 1.14–2.07), mononeuritis of upper limb and mononeuritis multiplex (1.36, 1.11–1.68), disorders of lipid metabolism (1.11, 1.01–1.23 ) and its subcategory other and unspecified hyperlipidemia (1.11, 1.01–1.24), and dysmetabolic syndrome X (1.74, 1.19–2.54). PC3 (high fatigue/moderate chemical inhalation stressor pattern) was associated with several migraine/headache conditions (aHR range: 1.18–1.60), disorders of lipid metabolism (1.11, 1.00–1.23) including other and unspecified hyperlipidemia (1.13, 1.01–1.26) , and overweight and obesity (1.13, 1.00–1.27). PC4 (high anxiety/modest fatigue stressor pattern) was associated with abnormality of gait (1.34, 1.03–1.73). PC5 (high back pain) was associated with mononeuritis of lower limb, several balance and gait-related conditions , thyroid disorders, and obesity (aHRs range: 1.16–1.67). Conclusion Oil spill response stressor patterns were associated with increased risks of multiple longer-term neurological and endocrine/metabolic conditions, with associations varying by PC.

Correction: From local discovery to global insights: deep-sea amphipod diversity in a high-seas marine protected area and its conservation implications - Anne-Nina Lörz; Laura Engel; Anna M. Jażdżewska; Stefanie Kaiser; Martin Schwentner (Frontiers in Marine Science, 2026)

Modelling health risks of urine-derived fertiliser application in urban green areas using quantitative microbial risk assessment - Johanna M. Engels; Frederic Leusch; Phil Choi; Patrick Smeets (Bioresource Technology, 2026)

The energy spectra of electron microbursts and their source populations - E.J. Engel; J. Sample; A.T. Johnson; M. Shumko; W.L. Wetzel; D.M. Klumpar (Advances in Space Research, 2026)

Evaluating the influence of climate inputs on WEPP predictions for a forest road in the Florida Panhandle, USA - Jingqiu Chen; Shuyuan Wang; William J. Elliot; Bernard A. Engel; Feng Pan; Yaoze Liu; Johnny M. Grace (Journal of Hydrology, 2026)

Corrigendum to ‘The environmental neuroactive chemicals list of prioritized substances for human biomonitoring and neurotoxicity testing: A database and high-throughput toxicokinetics approach’ [Environ. Res. 2025 (266) 120537] - Julia E. Rager; Lauren E. Koval; Elise Hickman; Caroline Ring; Taylor Teitelbaum; Todd Cohen; Giulia Fragola; Mark J. Zylka; Lawrence S. Engel; Kun Lu; Stephanie M. Engel (Environmental Research, 2026)

Decoding sebaceous gland functions and diseases: insights from domestic animals - Helga Pfannkuche; Juliane Maus; Kathrin M. Engel; Jürgen Schiller; Marlon R. Schneider (Veterinary Research Communications, 2026)
Skin sebaceous glands (SGs) synthesize and secrete sebum, a mixture of lipids and cellular debris that defends the external body surface against physicochemical challenges. Recent data define the SG as a dynamic entity with potential functions beyond skin protection, including immunomodulatory actions and the regulation of energy metabolism. We postulate that the SG also has important, unrecognized roles in physiological and pathological processes in domestic animals. Conversely, data derived from domestic animals may have translational relevance for humans. This review article summarizes SG structural and functional features in the most widespread species domesticated for food (cattle, sheep, goats, and pigs), work (horses), and companionship (dogs and cats). Our survey reveals hitherto unrecognized roles of the SG in diverse pathophysiological processes. Among other fascinating facts, we learn that sebum has an exquisite and unique lipid composition in each of the considered species. Furthermore, sebum is essential for e.g., wool production but also a carrier for the most important cat protein causing allergic reactions in humans, and dogs and cats may develop a SG-related skin illness resembling acne that is potentially relevant as a model for the human disease. This critical review provides a foundation for future interdisciplinary studies in a largely neglected area with great potential for advancing animal welfare and human health.

Increased P2X7 level does not affect anxiety or stress-coping behavior in male mice - Lidia Urbina-Treviño; Hao Tang; Iven-Alex von Mücke-Heim; Tobias Engel; Annette Nicke; Jan M. Deussing (Purinergic Signalling, 2026)
The P2RX7 gene has been linked to various neuropsychiatric disorders. In particular, the SNP rs2230912, which results in a glutamine-to-arginine substitution at position 460, has repeatedly been associated with mood disorders. Although this SNP per se does not affect receptor function, it tags a gain-of-function haplotype that has been shown to significantly enhance receptor activity. BAC-transgenic P2X7-reporter mice have proven to be valuable tools for monitoring P2X7 expression. Here, we exploited their capacity to simultaneously overexpress the receptor, thereby serving as gain-of-function models to assess the behavioral consequences of elevated P2X7 levels. We used the two currently available transgenic P2X7 reporter lines (sEGFP and P2X7-EGFP), which differ in their expression pattern, degree of overexpression, and co-expression of the neighbouring P2rx4 gene. Male sEGFP and P2X7-EGFP mice showed no alterations in general activity or in measures of anxiety-related or stress-coping behavior compared to their wild-type littermates. Only male P2X7-EGFP mice exhibited slightly delayed locomotor habituation to a novel environment. To what extent higher expression levels reflect enhanced receptor activity, as conveyed by the disease-associated gain-of-function haplotype, requires further investigation. Overall, these results indicate that P2X7 overexpression—whether at endogenous or ectopic sites, or in conjunction with P2X4—is not sufficient to substantially alter behavior of individually housed male mice under baseline conditions.

From local discovery to global insights: deep-sea amphipod diversity in a high-seas marine protected area and its conservation implications - Anne-Nina Lörz; Laura Engel; Anna M. Jażdżewska; Stefanie Kaiser; Martin Schwentner (Frontiers in Marine Science, 2026)
The deep ocean, while home to a remarkable diversity of life, remains one of the least understood environments on Earth. This profound lack of information hampers our ability to protect and manage deep-sea ecosystems effectively, especially as they face escalating threats from human activities such as resource extraction, pollution, and climate change. In light of these knowledge gaps, this study investigates the diversity of benthic amphipods collected from abyssal depths within the recently established North Atlantic Current and Evlanov Sea basin (NACES) high-seas marine protected area (MPA). Amphipods, with their brooding reproductive strategy and absence of a dispersive larval stage, are potentially limited in their distribution. This makes them valuable for biogeographic studies as biographic histories are maintained over longer periods of time. A total of 253 amphipod cytochrome c oxidase subunit I (COI) sequences were newly generated; these include 99 from the NACES MPA, 43 from the Labrador Sea, 42 from the Azores as well as 69 eusirids from other populations in the Atlantic, Pacific, Indian Ocean, and Antarctic. A single epibenthic sledge haul from the NACES MPA in 3,677 m depth revealed 47 amphipod molecular operational taxonomic units (MOTUs) from 98 sequenced individuals, with Chao1 estimates exceeding 120 species. This highlights unexpectedly high benthic diversity at local scales. The majority of these species could not be unambiguously assigned to known species, but many of these are probably new to science. Two of these species are formally described, Cleonardo helga sp. nov. and Cleonardo davinci sp. nov., and a dichotomous key to all known Cleonardo species worldwide is provided. Biogeographic links were studied for species of the family Eusiridae Stebbing, 1888 by comparing the NACES MOTUs to newly sequenced data from the North Atlantic and all existing COI sequences from GenBank and Barcode of Life Data Systems (BOLD). Of the eight NACES eusirid MOTUs, four were recorded also from other abyssal regions including the Labrador Sea, the Azores, the Arctic, and North and West Pacific. By linking the discovery of local species to broader global distribution patterns, this research enhances our understanding of deep-sea marine ecosystems and underscores the importance of conservation efforts in safeguarding these vulnerable marine habitats. ZooBank registration publication LSID - urn: lsid:zoobank.org:pub:99FFF47B-6389-49E7-A9D5-F47432FDE8CD.

Decreased Length of Locus Coeruleus Norepinephrine Axons and Increased Amyloid Beta Pathology in Male APP/PS1 Mice During Protracted Abstinence From Alcohol - Ivy J. Z. Garland; Shaydel Engel; Matthew Scalf; Nichole R. Payne; Anna M. Lee; Steven M. Graves (Neurotoxicity Research, 2026)
Alzheimer’s disease (AD) is the leading cause of dementia and evidence suggests that alcohol, the most commonly used addictive substance, may increase AD risk. Locus coeruleus (LC) neurons are the primary source of norepinephrine in the brain and these neurons degenerate early in AD. In rodent models, lesioning the LC increases amyloid beta (Aβ) pathology suggesting that LC integrity and norepinephrine signaling obstruct Aβ pathogenesis. We recently reported a decrease in the number of LC norepinephrine neurons and increased Aβ pathology when measured after protracted abstinence from chronic intermittent alcohol consumption in female APP/PS1 mice. Clinically, female subjects are at a higher risk for AD; additionally, female mice consume more alcohol than male mice making it unclear as to whether alcohol consumption would produce similar adverse outcomes in male subjects. To address this gap, male APP/PS1 and non-transgenic mice underwent chronic intermittent access (IA) to alcohol followed by protracted abstinence with water drinking controls run in parallel, consistent with our prior study. In contrast to our previous results with female mice, the number of LC norepinephrine neurons was unchanged in male APP/PS1 mice that had IA to alcohol; however, the length of LC axons was decreased and Aβ pathology was increased in male APP/PS1 mice that consumed alcohol. These data demonstrate that alcohol consumption during early adulthood results in negative consequences in male APP/PS1 mice, although the effect may not be as severe as previously observed in female mice.

Cancer Risk and Mortality Following Kaposi Sarcoma Among People with HIV in the United States, 2000 to 2019 - Sally Peprah; Eric A. Engels; Qianlai Luo; Analise Monterosso; Colby H. Cohen; Ruth M. Pfeiffer; Meredith S. Shiels (Cancer Causes & Control, 2026)
People with HIV (PWH) have increased Kaposi sarcoma (KS) risk. Among 2,645 PWH with KS in the United States HIV/AIDS Cancer Match Study, subsequent cancer risk was elevated 2.8-fold (95% confidence interval [CI]: 2.4–3.3) compared to PWH without KS. Mortality after KS declined 2000–2002 and 2012–2015 (hazard ratio = 0.64; 95%CI: 0.55–0.74).

The impact of feeding styles on unhealthy dietary intakes and weight-for-length z-scores: Investigating sweet beverages and snack food consumption during early childhood in a diverse sample - Catherine A. Serwatka; Lauren M. Smith; Amy M. Moore; Tarunjot Sethi; Hideko Engel; Amy R. Smith; Kai Ling Kong (Appetite, 2026)

The CALHM1 blocker CGP37157 increases seizure severity during status epilepticus in adult mice - Meghma Mitra; Amaya Sanz Rodriguez; Norman Delanty; Alan Beausang; Francesca M. Brett; Michael A. Farrell; Jane Cryan; Donncha F. O’Brien; David Henshall; Maria F. Cano-Abad; Tobias Engel (Purinergic Signalling, 2025)
Epilepsy is one of the most common chronic brain diseases affecting up to 70 million people worldwide. Major challenges of epilepsy treatment include the high pharmacoresistance in patients and the lack of disease-modification. Extracellular adenosine 3’triphosphate (ATP), a key neurotransmitter in the activation of the purinergic signalling system, is increasingly recognized to contribute to pathological brain hyperexcitability in epilepsy. Consequently, targeting ATP-release mechanisms may constitute a new therapeutic strategy for seizure control and epilepsy. The calcium channel, Calcium Homeostasis Modulator 1 (CALHM1), a voltage-gated, non-selective ion channel that permits the passage of various cations and small molecules, is expressed in neurons and plays an essential role during neuronal excitability and neurotransmission. In addition to ions, CALHM1 also allows the passage of ATP into the extracellular space, activating thereby purinergic receptors. Here, we tested if the pharmacological blocking of CALHM1 via CGP37157 (7-chloro-5-(2-chlorophenyl)-3,5-dihydro-4,1-benzothiazepin-2-(1H)-one) alters the severity of intra-amygdala kainic acid-induced status epilepticus. Our results show that CGP37157 increased the severity of seizures during status epilepticus. In addition, CALHM1 protein levels are down-regulated in the hippocampus in epileptic mice and Temporal Lobe Epilepsy (TLE) patients. In summary, our results identify CALHM1 as a new contributor to seizures and suggest targeting of CALHM1 as new treatment strategy for epilepsy.

Closely related native and non-native urban trees have similar leaf chemistries - Emily M. Herstoff; Liam D. Engel; Michael Tessler (Urban Forestry & Urban Greening, 2025)

OS02-07 The PARC Real-life Mixtures Project: Mixture Risk Assessment Results of the Case Studies on Pesticides, PFAS and Heavy Metals - H. McKeon; M. Carsique; P. Palmont; K. Machera; W. Bil; B. Bokkers; M. Mengelers; N. Vrijenhoek; E. McVey; A. Hernandez Jerez; E. Govarts; B. Cox; et al. (Toxicology Letters, 2025)

Association of oil spill cleanup-related hydrocarbon exposure with hypertension and blood pressure in the Gulf Long-term Follow-up Study - Opal P. Patel; Jessie K. Edwards; Anna M. Kucharska-Newton; Eric A. Whitsel; W. Braxton Jackson; Kaitlyn G. Lawrence; Patricia A. Stewart; Mark R. Stenzel; Lawrence S. Engel; Dale P. Sandler (Science of The Total Environment, 2025)

Early life phthalate exposure impacts gray matter and white matter volume in infants and young children - Emily J. Werder; Kun Lu; Chih-Wei Liu; Jake E. Thistle; Julia E. Rager; Gang Li; Zhengwang Wu; Tengfei Li; Li Wang; Dale P. Sandler; John H. Gilmore; Joseph Piven; et al. (Environmental Research, 2025)

Organic Geochemistry and Paleodepositional environment of the Mushorah Formation in Sufaya and Ain Zala oilfields, Northwestern Iraq - Mohamed W. Alkhafaji; Mohamed R. M. Ahmed; Taher Mahmood Taha; Anwaar S. Al-Maadhidi; Jacques Connan; Michael H. Engel (Carbonates and Evaporites, 2025)

The effect of climate at origin on Douglas-fir growth, leaf traits and embolism resistance along a rainfall gradient in Central Europe - Vincent P. Riedel; Patrick Engel; Pierre-André Waite; Roman M. Link; Randolf Schirmer; Joachim Hamberger; Bernhard Schuldt (Trees, 2025)
Key message In Douglas-fir grown in Central Europe, growth and specific leaf area differed between coastal and interior provenances but little intra-specific variability was found for the Huber value and xylem safety. Abstract In Central Europe, the economically most important timber species for roundwood production, Norway spruce, has been severely affected by recent global change-type drought events. Due to its large spatial distribution, Douglas-fir ( Pseudotsuga menziesii ) is considered for conversion to climate-resilient forests. Specifically, provenances from moister coastal and drier and colder interior regions might differ in drought tolerance traits. Here, we characterized aboveground biomass increment as well as leaf morphological and plant hydraulic traits in mature trees of 28 Douglas-fir provenances from three climate-at-origin groups across a climatic gradient in Central Europe, covering a precipitation range of 542 mm yr −1 . Irrespective of the gradient, the northern interior provenances had a 5.4 kg yr −1 lower aboveground biomass increment than the two coastal groups, accompanied by a 13% smaller specific leaf area. On the other hand, the Huber value, embolism resistance ( P 50 ) and leaf carbon isotope signature (δ 13 C) as proxy for long-term intrinsic water use efficiency did not differ between climate-origin groups. Across the gradient and within a climate-origin-group, no effect of climatic aridity on any of the traits covered was observed. Especially P 50 showed very little intra-specific variability, and our observed mean of −3.5 MPa is in the same range as P 50 -values for Douglas-fir recently reported from Europe. Our results for Douglas-fir support that xylem safety is a rather conservative and evolutionary canalized trait in conifers, while the Huber value revealed less plasticity as expected. Future studies are needed to test whether slower-growing interior provenances with thicker and smaller needles might be more drought tolerant and thus better suited for cultivation in the future climate of Central Europe although xylem safety does not differ.

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

The environmental neuroactive chemicals list of prioritized substances for human biomonitoring and neurotoxicity testing: A database and high-throughput toxicokinetics approach - Julia E. Rager; Lauren E. Koval; Elise Hickman; Caroline Ring; Taylor Teitelbaum; Todd Cohen; Giulia Fragola; Mark J. Zylka; Lawrence S. Engel; Kun Lu; Stephanie M. Engel (Environmental Research, 2025)

Early stakeholder involvement using Group Model Building to identify ecological research questions and nature management options - Lucien Hanssen; Luuk H. Leemans; M. Sabine Engel; Matthijs van der Geest; Leon P.M. Lamers; Alfons J.P. Smolders; Brigitta I. van Tussenbroek; Etienne Rouwette; Marjolijn J.A. Christianen; Marieke M. van Katwijk (Marine Pollution Bulletin, 2024)

The earliest large carpenter bee (Xylocopa) and its adhering pollen (Araliaceae, Theaceae) - Christian Geier; Michael S. Engel; Johannes M. Bouchal; Silvia Ulrich; Friðgeir Grímsson; Sonja Wedmann; Torsten Wappler (Palaeobiodiversity and Palaeoenvironments, 2024)
The association of pollinators with their host plants is a critical element of ecosystem functioning and one that is usually determined indirectly in the fossil record from specific morphological traits of flowers or putative pollinating animals. The exceptionally fine preservation at Messel, Germany, offers an excellent source of data on pollen from fossil flowers as well as preserved adhering to insects as direct evidence of their association with specific floral lineages. Here, we report on pollen recovered from the body and legs of a large carpenter bee (Apidae: Xylocopinae: Xylocopini) from the Eocene of Messel. The fossil is the earliest occurrence of the tribe Xylocopini and represents an extinct subgenus and species, described as Xylocopa ( Apocolyx ) primigenia subgen. et sp. nov. Two eudicot pollen types were recovered from the bee, one of the family Theaceae (Asterids: Ericales) and another of Araliaceae (Euasterids: Apiales). The pollen grains are compared with various extinct and extant pollen types, and data on floral visitors to modern theaceous and araliaceous flowers are explored in relation to understanding the association of the fossil carpenter with these floral types in the paratropical Eocene biota of Messel.

Urinary metabolite concentrations of phthalate and plasticizers in infancy and childhood in the UNC baby connectome project - Jake E. Thistle; Chih-Wei Liu; Julia E. Rager; Alison B. Singer; Dazhe Chen; Cherrel K. Manley; Joseph Piven; John H. Gilmore; Alexander P. Keil; Anne P. Starling; Hongtu Zhu; Weili Lin; et al. (Environmental Research, 2024)

Residential Proximity to Metal-Emitting Industries and Toenail Metal Concentration in the US Gulf States - Joyce J. Y. Lin; Emily J. Werder; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Aisha S. Dickerson; Lawrence S. Engel; Ana M. Rule (Exposure and Health, 2024)

S13-04 Towards interoperable modelling tools for integrative risk assessment – the PARC model network approach - J. Kruisselbrink; W. de Boer; M. van Lenthe; T. van Voorthuijsen; P. Palmont; L. Rodriguez Martin; D. Devriendt; E. Govarts; M. Carsique; A. Crépet; J. van Klaveren; J. Engel (Toxicology Letters, 2024)

S13-01 Strategy for real-life mixture risk assessment using HBM data - A. Crepet; M. Carsique; H. McKeon; A. Ratier; E. Govarts; B. Cox; M. Mengelers; K. Machera; J. Engel; J. van Klavaren (Toxicology Letters, 2024)

S13-03 Case studies showing the applicability of the mixture risk assessment strategy using HBM data - K. Machera; M. Carsique; W. Bil; P. Palmont; E. McVey; A. Hernandez Jerez; N. Vrijenhoek; B. Bokkers; H. McKeon; M. Mengelers; A. Ratier; J. Engel; et al. (Toxicology Letters, 2024)

Geochemical analysis of bituminous samples from the Pre-Pottery Neolithic B site of Nahal Efe (Northern Negev, Israel): Earliest evidence in the region and an example of alteration of the Dead Sea bitumen - Jacques Connan; Ferran Borrell; Jacob Vardi; Samuel Wolff; Steven M. Ortiz; Michael Engel; Renaud Gley; Alex Zumberge (Organic Geochemistry, 2024)

Large impacts and their contribution to the water budget of the Early Moon - T. Engels; J. Monteux; M. Boyet; M.A. Bouhifd (Icarus, 2024)

Perspectives on Conservation Impacts of the Global Primate Trade - Gal Badihi; Daniel R. K. Nielsen; Paul A. Garber; Mike Gill; Lisa Jones-Engel; Angela M. Maldonado; Kerry M. Dore; Jennifer D. Cramer; Susan Lappan; Francine Dolins; Emerson Y. Sy; Agustin Fuentes; et al. (International Journal of Primatology, 2024)
The global trade in nonhuman primates represents a substantial threat to ecosystem health, human health, and primate conservation worldwide. Most of the primate trade involves trade for pet-keeping, consumption, or biomedical experimentation. We present an overview of international primate trade through five case studies; each describes a different facet of this trade. We draw on published scientific literature, media outlets, and open access datasets, including the CITES Trade Database to build these case studies. Case study 1 describes the role of introduced island populations of Macaca and Chlorocebus in trade for biomedical experimentation; case study 2 covers the global health threats posed by the primate trade, including zoonotic disease transmission once animals enter the trade pipeline; case study 3 addresses the ways that changing patterns of primate trade, from local markets to online, have increased the demand for primates as pets; case study 4 recognizes the role that local environmental activism can play in mitigating trade; and case study 5 shows variation between global regions in their contribution to the primate trade. We recommend greater oversight of primate trade, especially domestic trade within primate range countries, and real-time reporting to CITES to accurately track primate trade. Effective conservation-focused regulations that can minimise the negative effects of primate trade must be tailored to specific regions and species and require transparency, careful regulation, field research, and an understanding of the magnitude of this trade.

Associations of a toenail metal mixture with attention and memory in the Gulf long-term follow-up (GuLF) study - Joyce J.Y. Lin; Jordan R. Kuiper; Aisha S. Dickerson; Jessie P. Buckley; Heather E. Volk; Diane S. Rohlman; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Lawrence S. Engel; Ana M. Rule (Science of The Total Environment, 2024)

Cross model validation for a diversified cropping system - Ixchel M. Hernández-Ochoa; Thomas Gaiser; Kathrin Grahmann; Anna Engels; Kurt-Christian Kersebaum; Sabine J. Seidel; Frank Ewert (European Journal of Agronomy, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Functional expression of the ATP-gated P2X7 receptor in human iPSC-derived astrocytes - Jaideep Kesavan; Orla Watters; Laura de Diego-Garcia; Aida Menéndez Méndez; Mariana Alves; Klaus Dinkel; Michael Hamacher; Jochen H. M. Prehn; David C. Henshall; Tobias Engel (Purinergic Signalling, 2024)
Activation of the ATP-gated P2X7 receptor (P2X7R), implicated in numerous diseases of the brain, can trigger diverse responses such as the release of pro-inflammatory cytokines, modulation of neurotransmission, cell proliferation or cell death. However, despite the known species-specific differences in its pharmacological properties, to date, most functional studies on P2X7R responses have been analyzed in cells from rodents or immortalised cell lines. To assess the endogenous and functional expression of P2X7Rs in human astrocytes, we differentiated human-induced pluripotent stem cells (hiPSCs) into GFAP and S100 β-expressing astrocytes. Immunostaining revealed prominent punctate P2X7R staining. P2X7R protein expression was also confirmed by Western blot. Importantly, stimulation with the potent non-selective P2X7R agonist 2′,3′-O-(benzoyl-4-benzoyl)-adenosine 5′- triphosphate (BzATP) or endogenous agonist ATP induced robust calcium rises in hiPSC-derived astrocytes which were blocked by the selective P2X7R antagonists AFC-5128 or JNJ-47965567. Our findings provide evidence for the functional expression of P2X7Rs in hiPSC-derived astrocytes and support their in vitro utility in investigating the role of the P2X7R and drug screening in disorders of the central nervous system (CNS).

Biodiversity responses to Lateglacial climate change in the subdecadally-resolved record of Lake Hämelsee (Germany) - S. Engels; C.S. Lane; W.Z. Hoek; I. Baneschi; A. Bouwman; E. Brogan; C. Bronk Ramsey; J. Collins; R. de Bruijn; A. Haliuc; O. Heiri; K. Hubay; et al. (Quaternary Science Reviews, 2024)

Differently expression of the metabotropic P2Y receptor family after hypoxia-induced seizures in neonates and seizure suppression via P2Y1 receptor agonism - Jonathon Smith; Beatriz Gil Lopez-Avila; Tobias Engel; Eva M. Jimenez Mateos; Mariana Alves (Purinergic Signalling, 2024)

Clusterin: a marker and mediator of chemoresistance in colorectal cancer - Sara Hlavca; Wing Hei Chan; Rebekah M. Engel; Helen E. Abud (Cancer and Metastasis Reviews, 2024)
Intra-tumoural heterogeneity and cancer cell plasticity in colorectal cancer (CRC) have been key challenges to effective treatment for patients. It has been suggested that a subpopulation of LGR5-expressing cancer stem cells (CSCs) is responsible for driving tumour relapse and therapy resistance in CRC. However, studies have revealed that the LGR5 +ve CSC population is highly sensitive to chemotherapy. It has been hypothesised that another subset of tumour cells can phenotypically revert to a stem-like state in response to chemotherapy treatment which replenishes the LGR5 +ve CSC population and maintains tumour growth. Recently, a unique stem cell population marked by enriched clusterin (CLU) expression and termed the revival stem cell (RevSC) was identified in the regenerating murine intestine. This CLU-expressing cell population is quiescent during homeostasis but has the ability to survive and regenerate other stem cells upon injury. More recently, the CLU +ve signature has been implicated in several adverse outcomes in CRC, including chemotherapy resistance and poor patient survival; however, the mechanism behind this remains undetermined. In this review, we discuss recent insights on CLU in CRC and its roles in enhancing the plasticity of cells and further consider the implications of CLU as a prospective target for therapeutic intervention.

A 1500‐year record of North Atlantic storm flooding from lacustrine sediments, Shetland Islands (UK) - Katharina Hess; Max Engel; Tasnim Patel; Polina Vakhrameeva; Andreas Koutsodendris; Eckehard Klemt; Thor H. Hansteen; Philipp Kempf; Sue Dawson; Isa Schön; Vanessa M. A. Heyvaert (Journal of Quaternary Science, 2024)
Severe storm flooding poses a major hazard to the coasts of north‐western Europe. However, the long‐term recurrence patterns of extreme coastal flooding and their governing factors are poorly understood. Therefore, high‐resolution sedimentary records of past North Atlantic storm flooding are required. This multi‐proxy study reconstructs storm‐induced overwash processes from coastal lake sediments on the Shetland Islands using grain‐size and geochemical data, and the re‐analysis of historical data. The chronostratigraphy is based on Bayesian age–depth modelling using accelerator mass spectrometry 14 C and 137 Cs data. A high XRF‐based Si/Ti ratio and the unimodal grain‐size distribution link the sand layers to the beach and thus storm‐induced overwash events. Periods with more frequent storm flooding occurred 980–1050, 1150–1300, 1450–1550, 1820–1900 and 1950–2000 ce, which is largely consistent with a positive North Atlantic Oscillation mode. The Little Ice Age (1400–1850 ce ) shows a gap of major sand layers suggesting a southward shift of storm tracks and a seasonal variance with more storm floods in spring and autumn. Warmer phases shifted winter storm tracks towards the north‐east Atlantic, indicating a possible trend for future storm‐track changes and increased storm flooding in the northern North Sea region.

A call to termitologists: it is time to abandon the use of “lower” and “higher” termites - T. F. Carrijo; M. S. Engel; T. Chouvenc; G. H. Gile; A. Mikaelyan; F. Dedeine; J. L. Ware; I. Haifig; A. Arab; J. P. Constantini; J. P. Souza; S. -B. Lee; et al. (Insectes Sociaux, 2023)

Isotopic and chemical signatures of high mountain rivers in catchments with contrasting glacier and rock glacier cover - S. Brighenti; M. Engel; R. Dinale; W. Tirler; G. Voto; F. Comiti (Journal of Hydrology, 2023)

The association of prenatal phthalates, organophosphorous pesticides, and organophosphate esters with early child language ability in Norway - Amanda M. Ramos; Amy H. Herring; Gro D. Villanger; Cathrine Thomsen; Amrit K. Sakhi; Enrique Cequier; Heidi Aase; Stephanie M. Engel (Environmental Research, 2023)

Traits of dominant plant species drive normalized difference vegetation index in grasslands globally - Thore Engel; Helge Bruelheide; Daniela Hoss; Francesco M. Sabatini; Jan Altman; Mohammed A. S. Arfin‐Khan; Erwin Bergmeier; Tomáš Černý; Milan Chytrý; Matteo Dainese; Jürgen Dengler; Jiri Dolezal; et al. (Global Ecology and Biogeography, 2023)
Aim Theoretical, experimental and observational studies have shown that biodiversity–ecosystem functioning (BEF) relationships are influenced by functional community structure through two mutually non‐exclusive mechanisms: (1) the dominance effect (which relates to the traits of the dominant species); and (2) the niche partitioning effect [which relates to functional diversity (FD)]. Although both mechanisms have been studied in plant communities and experiments at small spatial extents, it remains unclear whether evidence from small‐extent case studies translates into a generalizable macroecological pattern. Here, we evaluate dominance and niche partitioning effects simultaneously in grassland systems world‐wide. Location Two thousand nine hundred and forty‐one grassland plots globally. Time period 2000–2014. Major taxa studied Vascular plants. Methods We obtained plot‐based data on functional community structure from the global vegetation plot database “sPlot”, which combines species composition with plant trait data from the “TRY” database. We used data on the community‐weighted mean (CWM) and FD for 18 ecologically relevant plant traits. As an indicator of primary productivity, we extracted the satellite‐derived normalized difference vegetation index (NDVI) from MODIS. Using generalized additive models and deviation partitioning, we estimated the contributions of trait CWM and FD to the variation in annual maximum NDVI, while controlling for climatic variables and spatial structure. Results Grassland communities dominated by relatively tall species with acquisitive traits had higher NDVI values, suggesting the prevalence of dominance effects for BEF relationships. We found no support for niche partitioning for the functional traits analysed, because NDVI remained unaffected by FD. Most of the predictive power of traits was shared by climatic predictors and spatial coordinates. This highlights the importance of community assembly processes for BEF relationships in natural communities. Main conclusions Our analysis provides empirical evidence that plant functional community structure and global patterns in primary productivity are linked through the resource economics and size traits of the dominant species. This is an important test of the hypotheses underlying BEF relationships at the global scale.

Environmental Impacts on Skin Microbiomes of Sympatric High Arctic Salmonids - Erin F. Hamilton; Collin L. Juurakko; Katja Engel; Josh D. Neufeld; John M. Casselman; Charles W. Greer; Virginia K. Walker (Fishes, 2023)
In the region of King William Island, Nunavut, in the Canadian high Arctic, populations of salmonids including Arctic char (Salvelinus alpinus), cisco (Coregonus autumnalis and C. sardinella) as well as lake whitefish (C. clupeaformis) are diadromous, overwintering in freshwater and transitioning to saline waters following ice melt. Since these fish were sampled at the same time and from the same traditional fishing sites, comparison of their skin structures, as revealed by 16S rRNA gene sequencing, has allowed an assessment of influences on wild fish bacterial communities. Arctic char skin microbiota underwent turnover in different seasonal habitats, but these striking differences in dispersion and diversity metrics, as well as prominent taxa involving primarily Proteobacteria and Firmicutes, were less apparent in the sympatric salmonids. Not only do these results refute the hypothesis that skin communities, for the most part, reflect water microbiota, but they also indicate that differential recruitment of bacteria is influenced by the host genome and physiology. In comparison to the well-adapted Arctic char, lake whitefish at the northern edge of their range may be particularly vulnerable, and we suggest the use of skin microbiomes as a supplemental tool to monitor a sustainable Indigenous salmonid harvest during this period of change in the high Arctic.

Barriers and facilitators for participation in workplace health promotion programs: results from peer-to-peer interviews among employees - Denise J. M. Smit; Karin I. Proper; Josephine A. Engels; Jennifer M. D. Campmans; Sandra H. van Oostrom (International Archives of Occupational and Environmental Health, 2023)
Objective Workplace health promotion programs (WHPPs) have shown to be effective in improving lifestyle behaviors of employees. Despite potential benefits for employees, participation rates are generally low. The aim of this study was to gain deeper insight into barriers and facilitators for participation in WHPPs prior to implementation according to employees. Methods Peer-to-peer interviewing, a method derived from citizen science, was used to actively involve employees in the data collection. Employees working in the cleaning-, ICT- and facility-sector were trained to interview their co-workers. Interviews were recorded and transcribed verbatim. Thematic analysis was performed using the Consolidated Framework for Implementation Research (CFIR), complemented with the constructs ‘interpersonal factors’ and ‘intrapersonal factors’ from the social ecological model. Data were coded deductively and inductively, and rated by two researchers independently. Results Fourteen peer-interviewers conducted 62 peer-to-peer interviews. Main barriers for participation in WHPPs were an unsupportive organizational culture where lifestyle is not a common topic and programs that are not tailored to their needs. Support from peers and supervisors were facilitators. The availability of organizational resources, such as facilities and financial compensation, support participation. Conclusions To enhance participation of employees in WHPPs it is recommended to take into account the barriers and facilitators identified in this study. For instance, employees should be involved in the development and implementation of WHPPS by the employer and their needs and available resources should be taken into account. This may lead to more successful implementation and higher participation rates in future WHPPs.

Trophic ecology of three marine polychaete species: Evidence from laboratory experiments using stable isotope (15N, 13C), fatty acid (NLFA) analyses, and C and N stoichiometry - Nele Engel; M. Teresa Aguado; Mark Maraun (Marine Environmental Research, 2023)

Gestational organophosphate ester exposure and preschool attention-deficit/hyperactivity disorder in the Norwegian Mother, Father, and Child cohort study - Amber M. Hall; Amanda M. Ramos; Samantha SM. Drover; Giehae Choi; Alexander P. Keil; David B. Richardson; Chantel L. Martin; Andrew F. Olshan; Gro D. Villanger; Ted Reichborn-Kjennerud; Pål Zeiner; Kristin R. Øvergaard; et al. (International Journal of Hygiene and Environmental Health, 2023)

Lipid alterations by oxidative stress increase detached acrosomes after cryopreservation of semen in Holstein bulls - Ulrike Jakop; Kathrin M. Engel; Maren Hürland; Peter Müller; Jan-Henrik Osmers; Markus Jung; Martin Schulze (Theriogenology, 2023)

Detection of SARS-CoV-2 RNA in wastewater and comparison to COVID-19 cases in two sewersheds, North Carolina, USA - Alyssa M. Grube; Collin K. Coleman; Connor D. LaMontagne; Megan E. Miller; Nikhil P. Kothegal; David A. Holcomb; A. Denene Blackwood; Thomas J. Clerkin; Marc L. Serre; Lawrence S. Engel; Virginia T. Guidry; Rachel T. Noble; et al. (Science of The Total Environment, 2023)

Relative food abundance predicts greater binge-eating symptoms in subsequent hours among young adults experiencing food insecurity: Support for the “feast-or-famine” cycle hypothesis from an ecological momentary assessment study - Vivienne M. Hazzard; Katie A. Loth; Ross D. Crosby; Stephen A. Wonderlich; Scott G. Engel; Nicole Larson; Dianne Neumark-Sztainer (Appetite, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Seagrass ecosystem multifunctionality under the rise of a flagship marine megaherbivore - Marjolijn J. A. Christianen; Fee O. H. Smulders; Jan Arie Vonk; Leontine E. Becking; Tjeerd J. Bouma; Sabine M. Engel; Rebecca K. James; Mabel I. Nava; Jaco C. de Smit; Jurjan P. van der Zee; Per J. Palsbøll; Elisabeth S. Bakker (Global Change Biology, 2023)
Large grazers (megaherbivores) have a profound impact on ecosystem functioning. However, how ecosystem multifunctionality is affected by changes in megaherbivore populations remains poorly understood. Understanding the total impact on ecosystem multifunctionality requires an integrative ecosystem approach, which is especially challenging to obtain in marine systems. We assessed the effects of experimentally simulated grazing intensity scenarios on ecosystem functions and multifunctionality in a tropical Caribbean seagrass ecosystem. As a model, we selected a key marine megaherbivore, the green turtle, whose ecological role is rapidly unfolding in numerous foraging areas where populations are recovering through conservation after centuries of decline, with an increase in recorded overgrazing episodes. To quantify the effects, we employed a novel integrated index of seagrass ecosystem multifunctionality based upon multiple, well‐recognized measures of seagrass ecosystem functions that reflect ecosystem services. Experiments revealed that intermediate turtle grazing resulted in the highest rates of nutrient cycling and carbon storage, while sediment stabilization, decomposition rates, epifauna richness, and fish biomass are highest in the absence of turtle grazing. In contrast, intense grazing resulted in disproportionally large effects on ecosystem functions and a collapse of multifunctionality. These results imply that (i) the return of a megaherbivore can exert strong effects on coastal ecosystem functions and multifunctionality, (ii) conservation efforts that are skewed toward megaherbivores, but ignore their key drivers like predators or habitat, will likely result in overgrazing‐induced loss of multifunctionality, and (iii) the multifunctionality index shows great potential as a quantitative tool to assess ecosystem performance. Considerable and rapid alterations in megaherbivore abundance (both through extinction and conservation) cause an imbalance in ecosystem functioning and substantially alter or even compromise ecosystem services that help to negate global change effects. An integrative ecosystem approach in environmental management is urgently required to protect and enhance ecosystem multifunctionality.

Local biodiversity change reflects interactions among changing abundance, evenness, and richness - Shane A. Blowes; Gergana N. Daskalova; Maria Dornelas; Thore Engel; Nicholas J. Gotelli; Anne E. Magurran; Inês S. Martins; Brian McGill; Daniel J. McGlinn; Alban Sagouis; Hideyasu Shimadzu; Sarah R. Supp; et al. (Ecology, 2022)
Biodiversity metrics often integrate data on the presence and abundance of multiple species. Yet our understanding of covariation between changes to the numbers of individuals, the evenness of species relative abundances, and the total number of species remains limited. Using individual‐based rarefaction curves, we show how expected positive relationships among changes in abundance, evenness and richness arise, and how they can break down. We then examined interdependencies between changes in abundance, evenness and richness in more than 1100 assemblages sampled either through time or across space. As predicted, richness changes were greatest when abundance and evenness changed in the same direction, and countervailing changes in abundance and evenness acted to constrain the magnitude of changes in species richness. Site‐to‐site differences in abundance, evenness, and richness were often decoupled, and pairwise relationships between these components across assemblages were weak. In contrast, changes in species richness and relative abundance were strongly correlated for assemblages varying through time. Temporal changes in local biodiversity showed greater inertia and stronger relationships between the component changes when compared to site‐to‐site variation. Overall, local variation in assemblage diversity was rarely due to repeated passive samples from an approximately static species abundance distribution. Instead, changing species relative abundances often dominated local variation in diversity. Moreover, how changing relative abundances combined with changes to total abundance frequently determined the magnitude of richness changes. Embracing the interdependencies between changing abundance, evenness and richness can provide new information to better understand biodiversity change in the Anthropocene.

The serotonin receptor 3E variant is a risk factor for female IBS-D - Nikola Fritz; Sabrina Berens; Yuanjun Dong; Cristina Martínez; Stefanie Schmitteckert; Lesley A. Houghton; Miriam Goebel-Stengel; Verena Wahl; Maria Kabisch; Dorothea Götze; Mauro D’Amato; Tenghao Zheng; et al. (Journal of Molecular Medicine, 2022)
Irritable bowel syndrome (IBS) is a gut-brain disorder of multifactorial origin. Evidence of disturbed serotonergic function in IBS accumulated for the 5-HT 3 receptor family. 5-HT 3 Rs are encoded by HTR3 genes and control GI function, and peristalsis and secretion, in particular. Moreover, 5-HT 3 R antagonists are beneficial in the treatment of diarrhea predominant IBS (IBS-D). We previously reported on functionally relevant SNPs in HTR3A c.-42C > T (rs1062613), HTR3C p.N163K (rs6766410), and HTR3E c.*76G > A (rs56109847 = rs62625044) being associated with IBS-D, and the HTR3B variant p.Y129S (rs1176744) was also described within the context of IBS. We performed a multi-center study to validate previous results and provide further evidence for the relevance of HTR3 genes in IBS pathogenesis. Therefore, genotype data of 2682 IBS patients and 9650 controls from 14 cohorts (Chile, Germany (2), Greece, Ireland, Spain, Sweden (2), the UK (3), and the USA (3)) were taken into account. Subsequent meta-analysis confirmed HTR3E c.*76G > A (rs56109847 = rs62625044) to be associated with female IBS-D (OR = 1.58; 95% CI (1.18, 2.12)). Complementary expression studies of four GI regions (jejunum, ileum, colon, sigmoid colon) of 66 IBS patients and 42 controls revealed only HTR3E to be robustly expressed. On top, HTR3E transcript levels were significantly reduced in the sigma of IBS patients ( p = 0.0187); more specifically, in those diagnosed with IBS-D ( p = 0.0145). In conclusion, meta-analysis confirmed rs56109847 = rs62625044 as a risk factor for female IBS-D. Expression analysis revealed reduced HTR3E levels in the sigmoid colon of IBS-D patients, which underlines the relevance of HTR3E in the pathogenesis of IBS-D.

Evidence for preserved insulin responsiveness in the aging rat brain - Matthew G. Engel; Jeremy Smith; Kai Mao; Gabriela Farias Quipildor; Min-Hui Cui; Maria Gulinello; Craig A. Branch; Samuel E. Gandy; Derek M. Huffman (GeroScience, 2022)
Insulin appears to exert salutary effects in the central nervous system (CNS). Thus, brain insulin resistance has been proposed to play a role in brain aging and dementia but is conceptually complex and unlikely to fit classic definitions established in peripheral tissues. Thus, we sought to characterize brain insulin responsiveness in young (4–5 months) and old (24 months) FBN male rats using a diverse set of assays to determine the extent to which insulin effects in the CNS are impaired with age. When performing hyperinsulinemic-euglycemic clamps in rats, intracerebroventricular (ICV) infusion of insulin in old animals improved peripheral insulin sensitivity by nearly two-fold over old controls and comparable to young rats, suggesting preservation of this insulin-triggered response in aging per se ( p < 0.05). We next used an imaging-based approach by comparing ICV vehicle versus insulin and performed resting state functional magnetic resonance imaging (rs-fMRI) to evaluate age- and insulin-related changes in network connectivity within the default mode network. In aging, lower connectivity between the mesial temporal (MT) region and other areas, as well as reduced MT signal complexity, was observed in old rats, which correlated with greater cognitive deficits in old. Despite these stark differences, ICV insulin failed to elicit any significant alteration to the BOLD signal in young rats, while a significant deviation of the BOLD signal was observed in older animals, characterized by augmentation in regions of the septal nucleus and hypothalamus, and reduction in thalamus and nucleus accumbens. In contrast, ex vivo stimulation of hippocampus with 10 nM insulin revealed increased Akt activation in young ( p < 0.05), but not old rats. Despite similar circulating levels of insulin and IGF-1, cerebrospinal fluid concentrations of these ligands were reduced with age. Thus, these data highlight the complexity of capturing brain insulin action and demonstrate preserved or heightened brain responses to insulin with age, despite dampened canonical signaling, thereby suggesting impaired CNS input of these ligands may be a feature of reduced brain insulin action, providing further rationale for CNS replacement strategies.

Multiple regression analyses to determine the effect of sweating rate and tattoo characteristics on sweat outcome measures during exercise - David M. Keyes; Shyretha D. Brown; Michelle A. King; Megan D. Engel; Matthew Ciciora-Gold; Peter John D. De Chavez; Lindsay B. Baker (European Journal of Applied Physiology, 2022)
Purpose To compare local sweating rate (LSR) and local sweat sodium ([Na + ]), chloride ([Cl − ]), and potassium ([K + ]) concentrations of tattooed skin and contralateral non-tattooed skin during exercise. Methods Thirty-three recreational exercisers (17 men, 16 women) with ≥ 1 unilateral permanent tattoo on the torso/arms were tested during cycling, running, or fitness sessions (26 ± 4 °C and 54 ± 13% relative humidity). Forty-eight tattoos with a range of ink colors, ages (3 weeks to 20 years), and densities (10–100%) were included. Before exercise, the skin was cleaned with alcohol and patches (3 M Tegaderm + Pad) were placed on the tattooed and contralateral non-tattooed skin. LSR was calculated from sweat mass (0.80 ± 0.31 g), patch surface area (11.9 cm 2 ), and duration (62 ± 14 min). Sweat [Na + ], [Cl − ], and [K + ] were measured via ion chromatography. Results Based on the analysis of variance results, there were no differences between tattooed and non-tattooed skin for LSR (1.16 ± 0.52 vs. 1.12 ± 0.53 mg/cm 2 /min; p = 0.51), sweat [Na + ] (60.2 ± 23.5 vs. 58.5 ± 22.7 mmol/L; p = 0.27), sweat [Cl − ] (52.1 ± 22.4 vs. 50.6 ± 22.0 mmol/L; p = 0.31), or sweat [K + ] (5.8 ± 1.6 vs. 5.9 ± 1.4 mmol/L; p = 0.31). Multiple regression analyses suggested that younger tattoos were associated with higher sweat [Na + ] ( p = 0.045) and colorful tattoos were associated with higher sweat [Cl − ] ( p = 0.04) compared with contralateral non-tattooed skin. Otherwise, there were no effects of LSR or tattoo characteristics on regression models for LSR or sweat electrolyte concentrations. Conclusion There were no effects of tattoos on LSR and sweat [K + ] during exercise-induced sweating, but tattoo age and color had small effects on sweat [Na + ] and sweat [Cl − ], respectively. Clinical trial identifiers NCT04240951 was registered on January 27, 2020 and NCT04920266 was registered on June 9, 2021.

Reviewing the genetic evidence for sex-biased dispersal in elasmobranchs - Nicole M. Phillips; Floriaan Devloo-Delva; Carly McCall; Toby S. Daly-Engel (Reviews in Fish Biology and Fisheries, 2021)

Increasing prevalence of metastatic castration-resistant prostate cancer in a managed care population in the United States - Katrine L. Wallace; Adrienne Landsteiner; Scott H. Bunner; Nicole M. Engel-Nitz; Amy N. Luckenbaugh (Cancer Causes & Control, 2021)

Spatial distribution and sample size to estimate Euschistus heros population density in wild plants during off-season - Eduardo Engel; M. P. B. Pasini; A. D. C. Lúcio (Journal of Plant Diseases and Protection, 2021)

Site and plant community parameters drive the effect of vegetation on litterfall and nutrient inputs in restored tropical forests - Deivid L. Machado; Vera L. Engel; Diego S. Podadera; Luciane M. Sato; Ron G. M. de Goede; Luiz F. D. de Moraes; John A. Parrotta (Plant and Soil, 2021)

Understanding variability in greenhouse gas emission estimates of smallholder dairy farms in Indonesia - Titis Apdini; Windi Al Zahra; Simon J. Oosting; Imke J. M. de Boer; Marion de Vries; Bas Engel; Corina E. van Middelaar (The International Journal of Life Cycle Assessment, 2021)
Purpose Life cycle assessment studies on smallholder farms in tropical regions generally use data that is collected at one moment in time, which could hamper assessment of the exact situation. We assessed seasonal differences in greenhouse gas emissions (GHGEs) from Indonesian dairy farms by means of longitudinal observations and evaluated the implications of number of farm visits on the variance of the estimated GHGE per kg milk (GHGEI) for a single farm, and the population mean. Methods An LCA study was done on 32 smallholder dairy farms in the Lembang district area, West Java, Indonesia. Farm visits (FVs) were performed every 2 months throughout 1 year: FV1–FV3 (rainy season) and FV4–FV6 (dry season). GHGEs were assessed for all processes up to the farm-gate, including upstream processes (production and transportation of feed, fertiliser, fuel and electricity) and on-farm processes (keeping animals, manure management and forage cultivation). We compared means of GHGE per unit of fat-and-protein-corrected milk (FPCM) produced in the rainy and the dry season. We evaluated the implication of number of farm visits on the variance of the estimated GHGEI, and on the variance of GHGE from different processes. Results and discussion GHGEI was higher in the rainy (1.32 kg CO 2 -eq kg −1 FPCM) than in the dry (0.91 kg CO 2 -eq kg −1 FPCM) season ( P < 0.05). The between farm variance was 0.025 kg CO 2 -eq kg −1 FPCM in both seasons. The within farm variance in the estimate for the single farm mean decreased from 0.69 (1 visit) to 0.027 (26 visits) kg CO 2 -eq kg −1 FPCM (rainy season), and from 0.32 to 0.012 kg CO 2 -eq kg −1 FPCM (dry season). The within farm variance in the estimate for the population mean was 0.02 (rainy) and 0.01 (dry) kg CO 2 -eq kg −1 FPCM (1 visit), and decreased with an increase in farm visits. Forage cultivation was the main source of between farm variance, enteric fermentation the main source of within farm variance. Conclusions The estimated GHGEI was significantly higher in the rainy than in the dry season. The main contribution to variability in GHGEI is due to variation between observations from visits to the same farm. This source of variability can be reduced by increasing the number of visits per farm. Estimates for variation within and between farms enable a more informed decision about the data collection procedure.

Dissolved organic carbon ( DOC ) is essential to balance the metabolic demands of four dominant North‐Atlantic deep‐sea sponges - Martijn C. Bart; Benjamin Mueller; Titus Rombouts; Clea van de Ven; Gabrielle J. Tompkins; Ronald Osinga; Corina P.D. Brussaard; Barry MacDonald; Anja Engel; Hans Tore Rapp; Jasper M. de Goeij (Limnology and Oceanography, 2021)
Sponges are ubiquitous components of various deep‐sea habitats, including cold water coral reefs, and form deep‐sea sponge grounds. Although the deep sea is generally considered to be a food‐limited environment, these ecosystems are known to be hotspots of biodiversity and carbon cycling. To assess the role of sponges in the carbon cycling of deep‐sea ecosystems, we studied the carbon budgets of six dominant deep‐sea sponges of different phylogenetic origin, with various growth forms and hosting distinct associated microbial communities, in an ex situ aquarium setup. Additionally, we determined biomass metrics—planar surface area, volume, wet weight, dry weight (DW), ash‐free dry weight, and organic carbon (C) content—and conversion factors for all species. Oxygen (O 2 ) removal rates averaged 3.3 ± 2.8 μ mol O 2 g DW sponge h −1 (mean ± SD), live particulate (bacterio‐ and phytoplankton) organic carbon removal rates averaged 0.30 ± 0.39 μ mol C g DW sponge h −1 and dissolved organic carbon (DOC) removal rates averaged 18.70 ± 25.02 μ mol C g DW sponge h −1 . Carbon mass balances were calculated for four species and revealed that the sponges acquired 1.3–6.6 times the amount of carbon needed to sustain their minimal respiratory demands. These results indicate that irrespective of taxonomic class, growth form, and abundance of microbial symbionts, DOC is responsible for over 90% of the total net organic carbon removal of deep‐sea sponges and allows them to sustain themselves in otherwise food‐limited environments on the ocean floor.

Genetic evidence supports a range extension for the Brazilian cownose ray Rhinoptera brasiliensis in the western North Atlantic - Helen K. Weber; Christian M. Jones; Matthew J. Ajemian; Michael P. McCallister; Brent L. Winner; Gregg R. Poulakis; Dana M. Bethea; Lisa D. Hollensead; Daniel Zapf; John D. Swenson; Jill M. Hendon; Toby S. Daly‐Engel; et al. (Journal of Fish Biology, 2021)
We report 24 new records of the Brazilian cownose ray Rhinoptera brasiliensis outside its accepted geographic range. Sequencing of a 442‐base pair portion of the mitochondrial NADH dehydrogenase subunit 2 gene for 282 Rhinoptera samples revealed eight records off the east coast of the USA and 16 from the eastern Gulf of Mexico. Both sexes of all life stages were documented in all seasons over multiple years in the Indian River and Lake Worth lagoons, Florida, indicating that their range extends further in the western North Atlantic than previously described.

A multiscale framework for disentangling the roles of evenness, density, and aggregation on diversity gradients - Daniel J. McGlinn; Thore Engel; Shane A. Blowes; Nicholas J. Gotelli; Tiffany M. Knight; Brian J. McGill; Nathan J. Sanders; Jonathan M. Chase (Ecology, 2021)
Disentangling the drivers of diversity gradients can be challenging. The Measurement of Biodiversity (MoB) framework decomposes scale‐dependent changes in species diversity into three components of community structure: species abundance distribution (SAD), total community abundance, and within‐species spatial aggregation. Here we extend MoB from categorical treatment comparisons to quantify variation along continuous geographic or environmental gradients. Our approach requires sites along a gradient, each consisting of georeferenced plots of abundance‐based species composition data. We demonstrate our method using a case study of ants sampled along an elevational gradient of 28 sites in a mixed deciduous forest of the Great Smoky Mountains National Park, USA. MoB analysis revealed that decreases in ant species richness along the elevational gradient were associated with decreasing evenness and total number of species, which counteracted the modest increase in richness associated with decreasing spatial aggregation along the gradient. Total community abundance had a negligible effect on richness at all but the finest spatial grains, SAD effects increased in importance with sampling effort, and the aggregation effect had the strongest effect at coarser spatial grains. These results do not support the more‐individuals hypothesis, but they are consistent with a hypothesis of stronger environmental filtering at coarser spatial grains. Our extension of MoB has the potential to elucidate how components of community structure contribute to changes in diversity along environmental gradients and should be useful for a variety of assemblage‐level data collected along gradients.

Relationship Between Stink Bug Populations in Winter Shelters and Atmospheric Variables in Soybean Growing Areas in Southern Brazil - E Engel; M P B Pasini; A C Guma; L M Souza (Neotropical Entomology, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Seasonal habitat drives intestinal microbiome composition in anadromous Arctic char ( Salvelinus alpinus ) - Geraint Element; Katja Engel; Josh D. Neufeld; John M. Casselman; Peter van Coeverden de Groot; Charles W. Greer; Virginia K. Walker (Environmental Microbiology, 2020)
Summary Intestinal microbial communities from 362 anadromous Arctic char ( Salvelinus alpinus ) from the high Arctic Kitikmeot region, Nunavut, Canada, were characterized using high‐throughput 16S rRNA gene sequencing. The resulting bacterial communities were compared across four seasonal habitats that correspond to different stages of annual migration. Arctic char intestinal communities differed by sampling site, salinity and stages of freshwater residence. Although microbiota from fish sampled in brackish water were broadly consistent with taxa seen in other anadromous salmonids, they were enriched with putative psychrophiles, including the nonluminous gut symbiont Photobacterium iliopiscarium that was detected in >90% of intestinal samples from these waters. Microbiota from freshwater‐associated fish were less consistent with results reported for other salmonids, and highly variable, possibly reflecting winter fasting behaviour of these char. We identified microbiota links to age for those fish sampled during the autumn upriver migration, but little impact of the intestinal content and water microbiota on the intestinal community. The strongest driver of intestinal community composition was seasonal habitat, and this finding combined with identification of psychrophiles suggested that water temperature and migratory behaviour are key to understanding the relationship between Arctic char and their symbionts.

Stand growth and structure of mixed-species and monospecific stands of Scots pine (Pinus sylvestris L.) and oak (Q. robur L., Quercus petraea (Matt.) Liebl.) analysed along a productivity gradient through Europe - H. Pretzsch; M. Steckel; M. Heym; P. Biber; C. Ammer; M. Ehbrecht; K. Bielak; F. Bravo; C. Ordóñez; C. Collet; F. Vast; L. Drössler; et al. (European Journal of Forest Research, 2020)
Past failures of monocultures, caused by wind-throw or insect damages, and ongoing climate change currently strongly stimulate research into mixed-species stands. So far, the focus has mainly been on combinations of species with obvious complementary functional traits. However, for any generalization, a broad overview of the mixing reactions of functionally different tree species in different mixing proportions, patterns and under different site conditions is needed, including assemblages of species with rather similar demands on resources such as light. Here, we studied the growth of Scots pine and oak in mixed versus monospecific stands on 36 triplets located along a productivity gradient across Europe, reaching from Sweden to Spain and from France to Georgia. The set-up represents a wide variation in precipitation (456–1250 mm year −1 ), mean annual temperature (6.7–11.5 °C) and drought index by de Martonne (21–63 mm °C −1 ). Stand inventories and increment cores of trees stemming from 40- to 132-year-old, fully stocked stands on 0.04–0.94-ha-sized plots provided insight into how species mixing modifies stand growth and structure compared with neighbouring monospecific stands. On average, the standing stem volume was 436 and 360 m 3 ha −1 in the monocultures of Scots pine and oak, respectively, and 418 m 3 ha −1 in the mixed stands. The corresponding periodical annual volume increment amounted to 10.5 and 9.1 m 3 ha −1 year −1 in the monocultures and 10.5 m 3 ha −1 year −1 in the mixed stands. Scots pine showed a 10% larger quadratic mean diameter ( p < 0.05), a 7% larger dominant diameter ( p < 0.01) and a 9% higher growth of basal area and volume in mixed stands compared with neighbouring monocultures. For Scots pine, the productivity advantages of growing in mixture increased with site index ( p < 0.01) and water supply ( p < 0.01), while for oak they decreased with site index ( p < 0.01). In total, the superior productivity of mixed stands compared to monocultures increased with water supply ( p < 0.10). Based on 7843 measured crowns, we found that in mixture both species, but especially oak, had significantly wider crowns ( p < 0.001) than in monocultures. On average, we found relatively small effects of species mixing on stand growth and structure. Scots pine benefiting on rich, and oak on poor sites, allows for a mixture that is productive and most likely climate resistant all along a wide ecological gradient. We discuss the potential of this mixture in view of climate change.

Soothsaying DOM: A Current Perspective on the Future of Oceanic Dissolved Organic Carbon - Sasha Wagner; Florence Schubotz; Karl Kaiser; Christian Hallmann; Hannelore Waska; Pamela E. Rossel; Roberta Hansman; Marcus Elvert; Jack J. Middelburg; Anja Engel; Thomas M. Blattmann; Teresa S. Catalá; et al. (Frontiers in Marine Science, 2020)

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

The “Salcher” landslide observatory—experimental long-term monitoring in the Flysch Zone of Lower Austria - M. J. Stumvoll; E. Canli; A. Engels; B. Thiebes; B. Groiss; T. Glade; J. Schweigl; M. Bertagnoli (Bulletin of Engineering Geology and the Environment, 2020)
Shallow landslide processes in geologically prone areas are recognised to pose threat to both human life and property. As precipitation is one of the main triggers for landslides, hydro-meteorological interrelationships and related future changes regarding frequency and magnitude of landslide processes in particular are of major interest. Long-term monitoring investigations of active landslide sites can provide a better understanding of the kinematic behaviour and triggering conditions of slope instabilities induced by hydro-meteorological patterns. In this study, we present the installation and first results of a long-term monitoring setup in the Flysch Zone of Lower Austria equipped with a large variety of combined hydrological and geotechnical measuring techniques. The geological unit of the Flysch Zone, characterised by high contents of clay and the corresponding weathering products, is exceptionally prone to earth and debris slides which are mostly triggered by heavy precipitation events or snow melting. The landslide under investigation is situated in the heterogeneous lithology of Flysch deposits, surrounded by private property and without any agricultural usage. There is evidence of landslide activity since the 1950s. As it is showing only moderate displacement velocities (max. 20 cm in 2009), it represents a predestined study site for a long-term monitoring and the testing of new monitoring techniques. One of the main aims of this study is to characterise the internal structure, assess the current landslide dynamics and to analyse recent process activity by means of surface and subsurface monitoring installations. Surface methods currently include terrestrial laser scanning, GNSS and total station measurements. With these, surface movement rates of approx. 12 cm/6 months have been detected in the most active part of the landslide. Inclinometer measurements together with results from core drillings and penetrations tests suggest a complex, rotational landslide system with different shear zones, consisting of a more active part in the upper 3 m underlain by a less active part down to 9-m depth. As this monitoring site is designed to be operated for at least 10 years, information about its structure and high-resolution, multi-temporal data about its dynamics can be correlated with hydrological cause variables in the future. These insights and the exemplary nature of the study site regarding shallow landslide processes in Flysch deposits will be useful for the development of novel analysis methods for both Lower Austria as well as study sites with similar initial conditions.

Genomic changes underlying host specialization in the bee gut symbiont Lactobacillus Firm5 - Kirsten M. Ellegaard; Silvia Brochet; German Bonilla‐Rosso; Olivier Emery; Natasha Glover; Noushin Hadadi; Kamil S. Jaron; Jan R. van der Meer; Marc Robinson‐Rechavi; Vladimir Sentchilo; Florian Tagini; Philipp Engel (Molecular Ecology, 2019)
Bacteria that engage in long‐standing associations with particular hosts are expected to evolve host‐specific adaptations that limit their capacity to thrive in other environments. Consistent with this, many gut symbionts seem to have a limited host range, based on community profiling and phylogenomics. However, few studies have experimentally investigated host specialization of gut symbionts and the underlying mechanisms have largely remained elusive. Here, we studied host specialization of a dominant gut symbiont of social bees, Lactobacillus Firm5. We show that Firm5 strains isolated from honey bees and bumble bees separate into deep‐branching host‐specific phylogenetic lineages. Despite their divergent evolution, colonization experiments show that bumble bee strains are capable of colonizing the honey bee gut. However, they were less successful than honey bee strains, and competition with honey bee strains completely abolished their colonization. In contrast, honey bee strains of divergent phylogenetic lineages were able to coexist within individual bees. This suggests that both host selection and interbacterial competition play important roles in host specialization. Using comparative genomics of 27 Firm5 isolates, we found that the genomes of honey bee strains harbour more carbohydrate‐related functions than bumble bee strains, possibly providing a competitive advantage in the honey bee gut. Remarkably, most of the genes encoding carbohydrate‐related functions were not conserved among the honey bee strains, which suggests that honey bees can support a metabolically more diverse community of Firm5 strains than bumble bees. These findings advance our understanding of the genomic changes underlying host specialization.

Current and future ranges of an elusive North American insect using species distribution models - Daniel P. Silva; André F. A. Andrade; João P. J. Oliveira; Danielle M. Morais; Julya E. A. Vieira; Michael S. Engel (Journal of Insect Conservation, 2019)

Are the old International Board for Plant Genetic Resources (IBPGR) base collections available through the Plant Treaty’s multilateral system of access and benefit sharing? A review - Imke Thormann; Johannes M. M. Engels; Michael Halewood (Genetic Resources and Crop Evolution, 2019)

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Genetic variants in components of the NALCN–UNC80–UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies) - Nuria C. Bramswig; Aida M. Bertoli-Avella; Beate Albrecht; Aida I. Al Aqeel; Amal Alhashem; Nouriya Al-Sannaa; Maissa Bah; Katharina Bröhl; Christel Depienne; Nathalie Dorison; Diane Doummar; Nadja Ehmke; et al. (Human Genetics, 2018)

A spatially distributed Clark’s unit hydrograph based hybrid hydrologic model (Distributed-Clark) - Younghyun Cho; Bernard A. Engel; Venkatesh M. Merwade (Hydrological Sciences Journal, 2018)

De novo FBXO11 mutations are associated with intellectual disability and behavioural anomalies - Daniel Fritzen; Alma Kuechler; Mona Grimmel; Jessica Becker; Sophia Peters; Marc Sturm; Hela Hundertmark; Axel Schmidt; Martina Kreiß; Tim M. Strom; Dagmar Wieczorek; Tobias B. Haack; et al. (Human Genetics, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

A lake classification concept for a more accurate global estimate of the dissolved inorganic carbon export from terrestrial ecosystems to inland waters - Fabian Engel; Kaitlin J. Farrell; Ian M. McCullough; Facundo Scordo; Blaize A. Denfeld; Hilary A. Dugan; Elvira de Eyto; Paul C. Hanson; Ryan P. McClure; Peeter Nõges; Tiina Nõges; Elizabeth Ryder; et al. (The Science of Nature, 2018)

Natural and anthropogenic forcing of Holocene lake ecosystem development at Lake Uddelermeer (The Netherlands) - Stefan Engels; Rogier van Oostrom; Chiara Cherli; Jennifer A. J. Dungait; Boris Jansen; J. M. van Aken; Bas van Geel; Petra M. Visser (Journal of Paleolimnology, 2018)

Temporal stability and mixed-stock analyses of humpback whales (Megaptera novaeangliae) in the nearshore waters of the Western Antarctic Peninsula - G. R. Albertson; A. S. Friedlaender; D. J. Steel; A. Aguayo-Lobo; S. L. Bonatto; S. Caballero; R. Constantine; A. L. Cypriano-Souza; M. H. Engel; C. Garrigue; L. Flórez-González; D. W. Johnston; et al. (Polar Biology, 2018)

Modifiable and non-modifiable risk factors for preterm delivery among adolescent and young adult cancer survivors - Chelsea Anderson; Andrew B. Smitherman; Stephanie M. Engel; Hazel B. Nichols (Cancer Causes & Control, 2018)

Brain-Defective Insulin Signaling Is Associated to Late Cognitive Impairment in Post-Septic Mice - Fernanda S. Neves; Patrícia T. Marques; Fernanda Barros‑Aragão; José Bruno Nunes; Aline M. Venancio; Danielle Cozachenco; Rudimar L. Frozza; Giselle F. Passos; Robson Costa; Jade de Oliveira; Daiane F. Engel; Andreza F. De Bem; et al. (Molecular Neurobiology, 2018)

Serum cholesterol trajectories in the 10 years prior to lymphoma diagnosis - Sharon Hensley Alford; George Divine; Chun Chao; Laurel A. Habel; Nalini Janakiraman; Yun Wang; Heather Spencer Feigelson; Delia Scholes; Doug Roblin; Mara M. Epstein; Lawrence Engel; Suzanne Havstad; et al. (Cancer Causes & Control, 2018)

Latitude, temperature, and habitat complexity predict predation pressure in eelgrass beds across the Northern Hemisphere - Pamela L. Reynolds; John J. Stachowicz; Kevin Hovel; Christoffer Boström; Katharyn Boyer; Mathieu Cusson; Johan S. Eklöf; Friederike G. Engel; Aschwin H. Engelen; Britas Klemens Eriksson; F. Joel Fodrie; John N. Griffin; et al. (Ecology, 2018)
Latitudinal gradients in species interactions are widely cited as potential causes or consequences of global patterns of biodiversity. However, mechanistic studies documenting changes in interactions across broad geographic ranges are limited. We surveyed predation intensity on common prey (live amphipods and gastropods) in communities of eelgrass ( Zostera marina ) at 48 sites across its Northern Hemisphere range, encompassing over 37° of latitude and four continental coastlines. Predation on amphipods declined with latitude on all coasts but declined more strongly along western ocean margins where temperature gradients are steeper. Whereas in situ water temperature at the time of the experiments was uncorrelated with predation, mean annual temperature strongly positively predicted predation, suggesting a more complex mechanism than simply increased metabolic activity at the time of predation. This large‐scale biogeographic pattern was modified by local habitat characteristics; predation declined with higher shoot density both among and within sites. Predation rates on gastropods, by contrast, were uniformly low and varied little among sites. The high replication and geographic extent of our study not only provides additional evidence to support biogeographic variation in predation intensity, but also insight into the mechanisms that relate temperature and biogeographic gradients in species interactions.

Use of phytoproductivity data in the choice of native plant species to restore a degraded coal mining site amended with a stabilized industrial organic sludge - Claudete G. Chiochetta; Hela Toumi; Renata F. S. Böhm; Fernanda Engel; Gabriel Poyer-Radetski; Leonardo R. Rörig; Fabrizio Adani; Claudemir M. Radetski (Environmental Science and Pollution Research, 2017)

Expansion and fragment settlement of the non-native seagrass Halophila stipulacea in a Caribbean bay - Fee O. H. Smulders; J. Arie Vonk; M. Sabine Engel; Marjolijn J. A. Christianen (Marine Biology Research, 2017)

Manipulation of Non-random Species Loss in Natural Phytoplankton: Qualitative and Quantitative Evaluation of Different Approaches - Friederike G. Engel; Aleksandra M. Lewandowska; Sarah L. Eggers; Birte Matthiessen (Frontiers in Marine Science, 2017)

Genotypic and phenotypic changes in wild barley (Hordeum vulgare subsp. spontaneum) during a period of climate change in Jordan - I. Thormann; P. Reeves; S. Thumm; A. Reilley; J. M. M. Engels; C. M. Biradar; U. Lohwasser; A. Börner; K. Pillen; C. M. Richards (Genetic Resources and Crop Evolution, 2017)

Heterozygous HNRNPU variants cause early onset epilepsy and severe intellectual disability - Nuria C. Bramswig; Hermann-Josef Lüdecke; Fadi F. Hamdan; Janine Altmüller; Filippo Beleggia; Nursel H. Elcioglu; Catharine Freyer; Erica H. Gerkes; Yasemin Kendir Demirkol; Kelly G. Knupp; Alma Kuechler; Yun Li; et al. (Human Genetics, 2017)

A review of factors that influence the production of quality seed for long-term conservation in genebanks - N. Kameswara Rao; M. E. Dulloo; J. M. M. Engels (Genetic Resources and Crop Evolution, 2017)

Does affective touch influence the virtual reality full body illusion? - Jutta R. de Jong; Anouk Keizer; Manja M. Engel; H. Chris Dijkerman (Experimental Brain Research, 2017)

The Ocean's Vital Skin: Toward an Integrated Understanding of the Sea Surface Microlayer - Anja Engel; Hermann W. Bange; Michael Cunliffe; Susannah M. Burrows; Gernot Friedrichs; Luisa Galgani; Hartmut Herrmann; Norbert Hertkorn; Martin Johnson; Peter S. Liss; Patricia K. Quinn; Markus Schartau; et al. (Frontiers in Marine Science, 2017)

Heterozygosity for ARID2 loss-of-function mutations in individuals with a Coffin–Siris syndrome-like phenotype - Nuria C. Bramswig; O. Caluseriu; H.-J. Lüdecke; F. V. Bolduc; N. C. L. Noel; T. Wieland; H. M. Surowy; H.-J. Christen; H. Engels; T. M. Strom; D. Wieczorek (Human Genetics, 2017)

Identification of new TRIP12 variants and detailed clinical evaluation of individuals with non-syndromic intellectual disability with or without autism - Nuria C. Bramswig; H.-J. Lüdecke; M. Pettersson; B. Albrecht; R. A. Bernier; K. Cremer; E. E. Eichler; D. Falkenstein; J. Gerdts; S. Jansen; A. Kuechler; M. Kvarnung; et al. (Human Genetics, 2017)

Beyond Cuticular Hydrocarbons: Chemically Mediated Mate Recognition in the Subsocial Burying Beetle Nicrophorus vespilloides - Eva M. Keppner; Madlen Prang; Katharina C. Engel; Manfred Ayasse; Johannes Stökl; Sandra Steiger (Journal of Chemical Ecology, 2017)

A family-based study of gene variants and maternal folate and choline in neuroblastoma: a report from the Children’s Oncology Group - Angela L. Mazul; Anna Maria Siega-Riz; Clarice R. Weinberg; Stephanie M. Engel; Fei Zou; Kathryn S. Carrier; Patricia V. Basta; Zalman Vaksman; John M. Maris; Sharon J. Diskin; Charlene Maxen; Arlene Naranjo; et al. (Cancer Causes & Control, 2016)

The McGill Brisbane Symptom Score in relation to survival in pancreatic adenocarcinoma: a validation study - Suhail A. R. Doi; Luis Furuya-Kanamori; Jessica M. Engel; Mohammad H. Jamal; Rachel V. Stankowski; Jeffrey Barkun; Adedayo A. Onitilo (Cancer Causes & Control, 2016)

Performing monkeys of Bangladesh: characterizing their source and genetic variation - M. Kamrul Hasan; M. Mostafa Feeroz; Lisa Jones-Engel; Gregory A. Engel; Sharmin Akhtar; Sree Kanthaswamy; David Glenn Smith (Primates, 2016)

Retrofitting LID Practices into Existing Neighborhoods: Is It Worth It? - Timothy J. Wright; Yaoze Liu; Natalie J. Carroll; Laurent M. Ahiablame; Bernard A. Engel (Environmental Management, 2016)

Distributional modeling of Mantophasmatodea (Insecta: Notoptera): a preliminary application and the need for future sampling - Daniel P. Silva; Zander A. Spigoloni; Lucas M. Camargos; André Felipe Alves de Andrade; Paulo De Marco; Michael S. Engel (Organisms Diversity & Evolution, 2016)

Plant genetic resources collections and associated information as a baseline resource for genetic diversity studies: an assessment of the IBPGR-supported collections - I. Thormann; E. Fiorino; M. Halewood; J. M. M. Engels (Genetic Resources and Crop Evolution, 2015)

Influence of Removal of a Non-native Tree Species Mimosa caesalpiniifolia Benth. on the Regenerating Plant Communities in a Tropical Semideciduous Forest Under Restoration in Brazil - Diego S. Podadera; Vera L. Engel; John A. Parrotta; Deivid L. Machado; Luciane M. Sato; Giselda Durigan (Environmental Management, 2015)

‘Splitting versus lumping’: Temple–Baraitser and Zimmermann–Laband Syndromes - Nuria C. Bramswig; C. W. Ockeloen; J. C. Czeschik; A. J. van Essen; R. Pfundt; J. Smeitink; B. T. Poll-The; H. Engels; T. M. Strom; D. Wieczorek; T. Kleefstra; H.-J. Lüdecke (Human Genetics, 2015)

Antagomirs targeting microRNA-134 increase hippocampal pyramidal neuron spine volume in vivo and protect against pilocarpine-induced status epilepticus - Eva M. Jimenez-Mateos; Tobias Engel; Paula Merino-Serrais; Isabel Fernaud-Espinosa; Natalia Rodriguez-Alvarez; James Reynolds; Cristina R. Reschke; Ronan M. Conroy; Ross C. McKiernan; Javier deFelipe; David C. Henshall (Brain Structure and Function, 2015)

Altering Genomic Integrity: Heavy Metal Exposure Promotes Transposable Element-Mediated Damage - Maria E. Morales; Geraldine Servant; Catherine Ade; Astrid M. Roy-Engel (Biological Trace Element Research, 2015)

Overexpression of 14-3-3ζ Increases Brain Levels of C/EBP Homologous Protein CHOP - Gary P. Brennan; Eva M. Jimenez-Mateos; Amaya Sanz-Rodriguez; Claire M. Mooney; Guri Tzivion; David C. Henshall; Tobias Engel (Journal of Molecular Neuroscience, 2015)

In Vivo Quantification of the Apical Fixation Forces of Different Mitral Valved Stent Designs in the Beating Heart - S. Pokorny; K. Huenges; A. Engel; J. Gross; D. Frank; M. M. Morlock; J. Cremer; G. Lutter (Annals of Biomedical Engineering, 2015)

De novo mutations in beta-catenin (CTNNB1) appear to be a frequent cause of intellectual disability: expanding the mutational and clinical spectrum - Alma Kuechler; Marjolein H. Willemsen; Beate Albrecht; Carlos A. Bacino; Dennis W. Bartholomew; Hans van Bokhoven; Marie Jose H. van den Boogaard; Nuria Bramswig; Christian Büttner; Kirsten Cremer; Johanna Christina Czeschik; Hartmut Engels; et al. (Human Genetics, 2015)

Soil genotoxicity assessment—results of an interlaboratory study on the Vicia micronucleus assay in the context of ISO standardization - Sylvie Cotelle; Adrien Dhyèvre; Serge Muller; Pascale Chenon; Nicolas Manier; Pascal Pandard; Abdelwahad Echairi; Jérôme Silvestre; Maritxu Guiresse; Eric Pinelli; Lucia Giorgetti; Meri Barbafieri; et al. (Environmental Science and Pollution Research, 2015)

A new trap-jaw ant species of the genus Odontomachus (Hymenoptera: Formicidae: Ponerinae) from the Early Miocene (Burdigalian) of the Czech Republic - Torsten Wappler; Gennady M. Dlussky; Michael S. Engel; Jakub Prokop; Stanislav Knor (PalZ, 2014)

Fabrication and Evaluation of Nitinol Thin Film Heart Valves - K. Loger; R. Lima de Miranda; A. Engel; M. Marczynski-Bühlow; G. Lutter; E. Quandt (Cardiovascular Engineering and Technology, 2014)

A tailored implementation strategy to reduce the duration of intravenous antibiotic treatment in community-acquired pneumonia: a controlled before-and-after study - M. F. Engel; A. H. W. Bruns; M. E. J. L. Hulscher; C. A. J. M. Gaillard; S. U. C. Sankatsing; F. Teding van Berkhout; M. H. Emmelot-Vonk; E. M. Kuck; M. H. M. Steeghs; J. H. den Breeijen; R. K. Stellato; A. I. M. Hoepelman; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Diversity of crop development traits and nitrogen use efficiency among potato cultivars grown under contrasting nitrogen regimes - C. A. Ospina; E. T. Lammerts van Bueren; J. J. H. M. Allefs; B. Engel; P. E. L. van der Putten; C. G. van der Linden; P. C. Struik (Euphytica, 2014)

Modeling Water Quality Impacts of Cellulosic Biofuel Production from Corn Silage - Mark A. Thomas; Laurent M. Ahiablame; Bernard A. Engel; Indrajeet Chaubey; Nathan Mosier (BioEnergy Research, 2014)

Adolescents’ use of nicotine replacement therapy for smoking cessation: predictors of compliance trajectories - Charlotte S. Scherphof; Regina J. J. M. van den Eijnden; Peter Lugtig; Rutger C. M. E. Engels; Wilma A. M. Vollebergh (Psychopharmacology, 2014)

Variation in hair δ13C and δ15N values in long-tailed macaques (Macaca fascicularis) from Singapore - Michael A. Schillaci; J. Margaret Castellini; Craig A. Stricker; Lisa Jones-Engel; Benjamin P. Y.-H. Lee; Todd M. O’Hara (Primates, 2014)

Mechanisms linking plant community properties to soil aggregate stability in an experimental grassland plant diversity gradient - G. Pérès; D. Cluzeau; S. Menasseri; J. F. Soussana; H. Bessler; C. Engels; M. Habekost; G. Gleixner; A. Weigelt; W. W. Weisser; S. Scheu; N. Eisenhauer (Plant and Soil, 2013)

Seizures during antidepressant treatment in psychiatric inpatients—results from the transnational pharmacovigilance project “Arzneimittelsicherheit in der Psychiatrie” (AMSP) 1993–2008 - M. Köster; R. Grohmann; R. R. Engel; M. A. Nitsche; E. Rüther; D. Degner (Psychopharmacology, 2013)

A comparison of the strength of biodiversity effects across multiple functions - Eric Allan; Wolfgang W. Weisser; Markus Fischer; Ernst-Detlef Schulze; Alexandra Weigelt; Christiane Roscher; Jussi Baade; Romain L. Barnard; Holger Beßler; Nina Buchmann; Anne Ebeling; Nico Eisenhauer; et al. (Oecologia, 2013)

Complex origin of Trinitario-type Theobroma cacao (Malvaceae) from Trinidad and Tobago revealed using plastid genomics - Ji Yong Yang; Moira Scascitelli; Lambert A. Motilal; Saemundur Sveinsson; Johannes M. M. Engels; Nolan C. Kane; Hannes Dempewolf; Dapeng Zhang; Kamaldeo Maharaj; Quentin C. B. Cronk (Tree Genetics & Genomes, 2013)

Colorectal surveillance in Lynch syndrome families - Wouter H. de Vos tot Nederveen Cappel; Heikki J. Järvinen; Patrick M. Lynch; Christoph Engel; Jukka-Pekka Mecklin; Hans F. A. Vasen (Familial Cancer, 2013)

Positive urinary antigen tests for Streptococcus pneumoniae in community-acquired pneumonia: a 7-year retrospective evaluation of health care cost and treatment consequences - M. F. Engel; M. Velzen; A. I. M. Hoepelman; S. Thijsen; J. J. Oosterheert (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Coral overgrowth by an encrusting red alga (Ramicrusta sp.): a threat to Caribbean reefs? - Caren E. Eckrich; M. Sabine Engel (Coral Reefs, 2013)

17 novel polymorphic microsatellite markers for the giant water bug, Abedus herberti (Belostomatidae) - T. S. Daly-Engel; R. L. Smith; D. S. Finn; M. E. Knoderbane; I. C. Phillipsen; D. A. Lytle (Conservation Genetics Resources, 2012)

Effects of rising temperature on pelagic biogeochemistry in mesocosm systems: a comparative analysis of the AQUASHIFT Kiel experiments - Julia Wohlers-Zöllner; Antje Biermann; Anja Engel; Petra Dörge; Aleksandra M. Lewandowska; Markus von Scheibner; Ulf Riebesell (Marine Biology, 2012)

Effectiveness of Low Impact Development Practices: Literature Review and Suggestions for Future Research - Laurent M. Ahiablame; Bernard A. Engel; Indrajeet Chaubey (Water, Air, & Soil Pollution, 2012)

Nitrogen uptake by grassland communities: contribution of N2 fixation, facilitation, complementarity, and species dominance - Holger Bessler; Yvonne Oelmann; Christiane Roscher; Nina Buchmann; Michael Scherer-Lorenzen; Ernst-Detlef Schulze; Vicky M. Temperton; Wolfgang Wilcke; Christof Engels (Plant and Soil, 2012)

Greenhouse gas emissions of two mechanised wood harvesting methods in comparison with the use of draft horses for logging - A. -M. Engel; J. Wegener; M. Lange (European Journal of Forest Research, 2012)

Diabetes and cancer II: role of diabetes medications and influence of shared risk factors - Adedayo A. Onitilo; Jessica M. Engel; Ingrid Glurich; Rachel V. Stankowski; Gail M. Williams; Suhail A. Doi (Cancer Causes & Control, 2012)

Diabetes and cancer I: risk, survival, and implications for screening - Adedayo A. Onitilo; Jessica M. Engel; Ingrid Glurich; Rachel V. Stankowski; Gail M. Williams; Suhail A. Doi (Cancer Causes & Control, 2012)

Validation of three BRCA1/2 mutation-carrier probability models Myriad, BRCAPRO and BOADICEA in a population-based series of 183 German families - S. M. Schneegans; A. Rosenberger; U. Engel; M. Sander; G. Emons; M. Shoukier (Familial Cancer, 2012)

Assessing the potential for post‐copulatory sexual selection in elasmobranchs - J. L. Fitzpatrick; R. M. Kempster; T. S. Daly‐Engel; S. P. Collin; J. P. Evans (Journal of Fish Biology, 2012)
This review highlights the potential role that post‐copulatory sexual selection plays in elasmobranch reproductive systems and the utility of this group to further understanding of evolutionary responses to the post‐copulatory processes of sperm competition and cryptic female choice. The growing genetic evidence for female multiple mating (polyandry) in elasmobranchs is summarized. While polyandry appears to be common in this group, rates of multiple paternity are highly variable between species suggesting that there is large variance in the strength of post‐copulatory sexual selection among elasmobranchs. Possible adaptations of traits important for post‐copulatory sexual selection are then considered. Particular emphasis is devoted to explore the potential for sperm competition and cryptic female choice to influence the evolution of testes size, sperm morphology, genital morphology and sperm storage organs. Finally, it is argued that future work should take advantage of the wealth of information on these reproductive traits already available in elasmobranchs to gain a better understanding of how post‐copulatory sexual selection operates in this group.

A Hydrological Budget (2002–2008) for a Large Subtropical Wetland Ecosystem Indicates Marine Groundwater Discharge Accompanies Diminished Freshwater Flow - Amartya K. Saha; Christopher S. Moses; René M. Price; Victor Engel; Thomas J. Smith; Gordon Anderson (Estuaries and Coasts, 2012)

Description of an ancient social bee trapped in amber using diagnostic radioentomology - M. K. Greco; P. M. Welz; M. Siegrist; S. J. Ferguson; P. Gallmann; D. W. Roubik; M. S. Engel (Insectes Sociaux, 2011)

Crustose, calcareous algal bloom (Ramicrusta sp.) overgrowing scleractinian corals, gorgonians, a hydrocoral, sponges, and other algae in Lac Bay, Bonaire, Dutch Caribbean - C. E. Eckrich; M. S. Engel; R. B. J. Peachey (Coral Reefs, 2011)

The role of the disulfide bond in the interaction of islet amyloid polypeptide with membranes - Lucie Khemtémourian; Maarten F. M. Engel; John A. W. Kruijtzer; Jo W. M. Höppener; Rob M. J. Liskamp; J. Antoinette Killian (European Biophysics Journal, 2010)

Recommendations to improve identification of hereditary and familial colorectal cancer in Europe - H. F. A. Vasen; G. Möslein; A. Alonso; S. Aretz; I. Bernstein; L. Bertario; I. Blanco; S. Bulow; J. Burn; G. Capella; C. Colas; C. Engel; et al. (Familial Cancer, 2010)

Factors Controlling Surface Water Flow in a Low-gradient Subtropical Wetland - Guoqing He; Victor Engel; Lynn Leonard; Alex Croft; Daniel Childers; Michael Laas; Yang Deng; Helena M. Solo-Gabriele (Wetlands, 2010)

Plant diversity effects on soil microorganisms support the singular hypothesis - N. Eisenhauer; H. Beßler; C. Engels; G. Gleixner; M. Habekost; A. Milcu; S. Partsch; A. C. W. Sabais; C. Scherber; S. Steinbeiss; A. Weigelt; W. W. Weisser; et al. (Ecology, 2010)
The global decline in biodiversity has generated concern over the consequences for ecosystem functioning and services. Although ecosystem functions driven by soil microorganisms such as plant productivity, decomposition, and nutrient cycling are of particular importance, interrelationships between plant diversity and soil microorganisms are poorly understood. We analyzed the response of soil microorganisms to variations in plant species richness (1–60) and plant functional group richness (1–4) in an experimental grassland system over a period of six years. Major abiotic and biotic factors were considered for exploring the mechanisms responsible for diversity effects. Further, microbial growth characteristics were assessed following the addition of macronutrients. Effects of plant diversity on soil microorganisms were most pronounced in the most diverse plant communities though differences only became established after a time lag of four years. Differences in microbial growth characteristics indicate successional changes from a disturbed (zymogeneous) to an established (autochthonous) microbial community four years after establishment of the experiment. Supporting the singular hypothesis for plant diversity, the results suggest that plant species are unique, each contributing to the functioning of the belowground system. The results reinforce the need for long‐term biodiversity experiments to fully appreciate consequences of current biodiversity loss for ecosystem functioning.

What Have We Learned from the Congenital Myasthenic Syndromes - Andrew G. Engel; Xin-Ming Shen; Duygu Selcen; Steven M. Sine (Journal of Molecular Neuroscience, 2010)

Feeding grounds of the western South Atlantic humpback whale population - M. H. ENGEL; A. R. MARTIN (Marine Mammal Science, 2009)

Aboveground overyielding in grassland mixtures is associated with reduced biomass partitioning to belowground organs - Holger Bessler; Vicky M. Temperton; Christiane Roscher; Nina Buchmann; Bernhard Schmid; Ernst-Detlef Schulze; Wolfgang W. Weisser; Christof Engels (Ecology, 2009)
We investigated effects of plant species richness in experimental grassland plots on annual above‐ and belowground biomass production estimated from repeated harvests and ingrowth cores, respectively. Aboveground and total biomass production increased with increasing plant species richness while belowground production remained constant. Root to shoot biomass production ratios (R/S) in mixtures were lower than expected from monoculture performance of the species present in the mixtures, showing that interactions among species led to reduced biomass partitioning to belowground organs. This change in partitioning to belowground organs was not confined to mixtures with legumes, but also measured in mixtures without legumes, and correlated with aboveground overyielding in mixtures. It is suggested that species‐rich communities invest less in belowground biomass than do monocultures to extract soil resources, thus leading to increased investment into aboveground organs and overyielding.

Demise of reef-flat carbonate accumulation with late Holocene sea-level fall: evidence from Molokai, Hawaii - M. S. Engels; C. H. Fletcher; M. Field; C. L. Conger; C. Bochicchio (Coral Reefs, 2008)

Plant diversity positively affects short‐term soil carbon storage in experimental grasslands - SIBYLLE STEINBEISS; HOLGER BEßLER; CHRISTOF ENGELS; VICKY M. TEMPERTON; NINA BUCHMANN; CHRISTIANE ROSCHER; YVONNE KREUTZIGER; JUSSI BAADE; MAIKE HABEKOST; GERD GLEIXNER (Global Change Biology, 2008)
Increasing atmospheric CO 2 concentration and related climate change have stimulated much interest in the potential of soils to sequester carbon. In ‘The Jena Experiment’, a managed grassland experiment on a former agricultural field, we investigated the link between plant diversity and soil carbon storage. The biodiversity gradient ranged from one to 60 species belonging to four functional groups. Stratified soil samples were taken to 30 cm depth from 86 plots in 2002, 2004 and 2006, and organic carbon contents were determined. Soil organic carbon stocks in 0–30 cm decreased from 7.3 kg C m −2 in 2002 to 6.9 kg C m −2 in 2004, but had recovered to 7.8 kg C m −2 by 2006. During the first 2 years, carbon storage was limited to the top 5 cm of soil while below 10 cm depth, carbon was lost probably as short‐term effect of the land use change. After 4 years, carbon stocks significantly increased within the top 20 cm. More importantly, carbon storage significantly increased with sown species richness (log‐transformed) in all depth segments and even carbon losses were significantly smaller with higher species richness. Although increasing species diversity increased root biomass production, statistical analyses revealed that species diversity per se was more important than biomass production for changes in soil carbon. Below 20 cm depth, the presence of one functional group, tall herbs, significantly reduced carbon losses in the beginning of the experiment. Our analysis indicates that plant species richness and certain plant functional traits accelerate the build‐up of new carbon pools within 4 years. Additionally, higher plant diversity mitigated soil carbon losses in deeper horizons. This suggests that higher biodiversity might lead to higher soil carbon sequestration in the long‐term and therefore the conservation of biodiversity might play a role in greenhouse gas mitigation.

Diversity of proteolytic community encoding for subtilisin in an arable field: spatial and temporal variability - M. Mrkonjic Fuka; M. Engel; F. Haesler; G. Welzl; J. C. Munch; M. Schloter (Biology and Fertility of Soils, 2008)

Intraregional variability in chironomid-inferred temperature estimates and the influence of river inundations on lacustrine chironomid assemblages - S. Engels; S. J. P. Bohncke; O. Heiri; M. Nyman (Journal of Paleolimnology, 2008)

Microbial community shifts in Pythium ultimum-inoculated suppressive substrates - A. Hagn; M. Engel; B. Kleikamp; J. C. Munch; M. Schloter; C. Bruns (Biology and Fertility of Soils, 2008)

Distribution, substrate preference and habitat enhancement of the isopod Austridotea lacustris in Tomahawk Lagoon, Otago, New Zealand - Celine M. Dufour; Nikita M. Engels; Carolyn W. Burns (New Zealand Journal of Marine and Freshwater Research, 2007)
Aquatic isopods are cryptic, semibenthic components of food webs in coastal water bodies in southern New Zealand. The distribution and abundance of endemic Austridotea lacustris in a modified, urban coastal lagoon were related to selected environmental and habitat variables in field studies and laboratory experiments. Isopods were four times more abundant on lumps of roading conglomerate used in shoreline consolidation than on bricks and natural rocks. Isopod densities were unrelated to the size of the substrate units or their development of biofilm, a major food source for isopods. In experiments to test settlement behaviour with concrete and wood substrates of different structural complexity (with and without holes), isopods showed clear preferences for wood over concrete substrates, and for more complex (more holes per unit area) than less complex (few, or no holes) wood substrates. By increasing the habitat complexity in coastal water bodies, it might be possible to restore and increase populations of aquatic isopods.

Patients as real time teachers - Bernard M. Bandman; Celia Engel Bandman; Nathan Pennell; Lidia Schapira (Journal of Cancer Education, 2007)

In situ detection of novel Acidobacteria in microbial mats from a chemolithoautotrophically based cave ecosystem (Lower Kane Cave, WY, USA) - Daniela B. Meisinger; Johannes Zimmermann; Wolfgang Ludwig; Karl‐Heinz Schleifer; Gerhard Wanner; Michael Schmid; Philip C. Bennett; Annette S. Engel; Natuschka M. Lee (Environmental Microbiology, 2007)
Summary Lower Kane Cave, Wyoming (USA), has hydrogen sulfide‐bearing springs that discharge into the cave passage. The springs and cave stream harbour white filamentous microbial mats dominated by Epsilonproteobacteria . Recently, novel 16S rRNA gene sequences from the phylum Acidobacteria , subgroup 7, were found in these cave mats. Although Acidobacteria are ubiquitously distributed in many terrestrial and marine habitats, little is known about their ecophysiology. To investigate this group in Lower Kane Cave in more detail, a full‐cycle rRNA approach was applied based on 16S and 23S rRNA gene clone libraries and the application of novel probes for fluorescence in situ hybridization . The 16S and 23S rRNA gene clone libraries yielded seven and six novel acidobacterial operational taxonomic units (OTUs) respectively. The majority of the OTUs were affiliated with subgroups 7 and 8. One OTU was affiliated with subgroup 6, and one OTU could not be assigned to any of the present acidobacterial subgroups. Fluorescence in situ hybridization distinguished two morphologically distinct, rod‐shaped cells of the acidobacterial subgroups 7 and 8. Although the ecophysiology of Acidobacteria from Lower Kane Cave will not be fully resolved until cultures are obtained, acidobacterial cells were always associated with the potentially chemolithoautotrophic epsilon‐ or gammaproteobacterial filaments, suggesting perhaps a lifestyle based on heterotrophy or chemoorganotrophy.

Adding value to cocoa (Theobroma cacao L.) germplasm information with domestication history and admixture mapping - Maria Marcano; Tatiana Pugh; Emile Cros; Sonia Morales; Elvis A. Portillo Páez; Brigitte Courtois; Jean Christophe Glaszmann; Jan M. M. Engels; Wilbert Phillips; Carlos Astorga; Ange Marie Risterucci; Olivier Fouet; et al. (Theoretical and Applied Genetics, 2007)

Foraging ability in the scorpionfly Panorpa vulgaris: individual differences and heritability - M. Missoweit; S. Engels; K. P. Sauer (Behavioral Ecology and Sociobiology, 2006)

Centres of Crop Diversity and/or Origin, Genetically Modified Crops and Implications for Plant Genetic Resources Conservation - J. M. M. Engels; A. W. Ebert; I. Thormann; M. C. de Vicente (Genetic Resources and Crop Evolution, 2006)

Effects of selection felling and gap felling on forest arthropod communities: a case study in a spruce-beech stand of southern Bavaria - M. Goßner; K. Engel; U. Ammer (European Journal of Forest Research, 2006)

Goodbye or welcome Gondwana? – insights into the phylogenetic biogeography of the leafy liverwort Plagiochila with a description of Proskauera, gen. nov. (Plagiochilaceae, Jungermanniales) - J. Heinrichs; M. Lindner; H. Groth; J. Hentschel; K. Feldberg; C. Renker; J. J. Engel; M. von Konrat; D. G. Long; H. Schneider (Plant Systematics and Evolution, 2006)

Spatial-Scale Effects on Relative Importance of Physical Habitat Predictors of Stream Health - Emmanuel A. Frimpong; Trent M. Sutton; Bernard A. Engel; Thomas P. Simon (Environmental Management, 2005)

Functional and structural characterization of the minimal Sec translocase of the hyperthermophile Thermotoga maritima - Monika G. Pretz; Hervé Remigy; Jelto Swaving; Sonja V. Albers; Victoria G. Garrido; Mohamed Chami; Andreas Engel; Arnold J. M. Driessen (Extremophiles, 2005)

Grain yield and kernel weight of two maize genotypes differing in nitrogen use efficiency at various levels of nitrogen and carbohydrate availability during flowering and grain filling - I. A. Paponov; P. Sambo; G. Schulte auf′m. Erley; T. Presterl; H. H. Geiger; C. Engels (Plant and Soil, 2005)

Kernel set in maize genotypes differing in nitrogen use efficiency in response to resource availability around flowering - I. A. Paponov; P. Sambo; G. Schulte auf′m. Erley; T. Presterl; H. H. Geiger; C. Engels (Plant and Soil, 2005)

Increased leaf area dominates carbon flux response to elevated CO 2 in stands of Populus deltoides (Bartr.) - Ramesh Murthy; Greg Barron‐Gafford; Phillip M. Dougherty; Victor C. Engel; Katie Grieve; Linda Handley; Christie Klimas; Mark J. Potosnak; Stanley J. Zarnoch; Jianwei Zhang (Global Change Biology, 2005)
We examined the effects of atmospheric vapor pressure deficit (VPD) and soil moisture stress (SMS) on leaf‐ and stand‐level CO 2 exchange in model 3‐year‐old coppiced cottonwood ( Populus deltoides Bartr.) plantations using the large‐scale, controlled environments of the Biosphere 2 Laboratory. A short‐term experiment was imposed on top of continuing, long‐term CO 2 treatments (43 and 120 Pa), at the end of the growing season. For the experiment, the plantations were exposed for 6–14 days to low and high VPD (0.6 and 2.5 kPa) at low and high volumetric soil moisture contents (25–39%). When system gross CO 2 assimilation was corrected for leaf area, system net CO 2 exchange (SNCE), integrated daily SNCE, and system respiration increased in response to elevated CO 2 . The increases were mainly as a result of the larger leaf area developed during growth at high CO 2 , before the short‐term experiment; the observed decline in responses to SMS and high VPD treatments was partly because of leaf area reduction. Elevated CO 2 ameliorated the gas exchange consequences of water stress at the stand level, in all treatments. The initial slope of light response curves of stand photosynthesis (efficiency of light use by the stand) increased in response to elevated CO 2 under all treatments. Leaf‐level net CO 2 assimilation rate and apparent quantum efficiency were consistently higher, and stomatal conductance and transpiration were significantly lower, under high CO 2 in all soil moisture and VPD combinations (except for conductance and transpiration in high soil moisture, low VPD). Comparisons of leaf‐ and stand‐level gross CO 2 exchange indicated that the limitation of assimilation because of canopy light environment (in well‐irrigated stands; ratio of leaf : stand=3.2–3.5) switched to a predominantly individual leaf limitation (because of stomatal closure) in response to water stress (leaf : stand=0.8–1.3). These observations enabled a good prediction of whole stand assimilation from leaf‐level data under water‐stressed conditions; the predictive ability was less under well‐watered conditions. The data also demonstrated the need for a better understanding of the relationship between leaf water potential, leaf abscission, and stand LAI.

Effects of caspofungin (MK-0991) and anidulafungin (LY303366) on phagocytosis, oxidative burst and killing of Candida albicans by human phagocytes - U. Frank; M. Greiner; I. Engels; F.D. Daschner (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Remote sensing as a tool for achieving and monitoring progress toward sustainability - Gilbert L. Rochon; Chris J. Johannsen; David A. Landgrebe; Bernard A. Engel; Jonathan M. Harbor; Sarada Majumder; Larry L. Biehl (Clean Technologies and Environmental Policy, 2003)

A NOVEL BEHAVIOR OBSERVED IN HUMPBACK WHALES ON WINTERING GROUNDS AT ABROLHOS BANK (BRAZIL) - Maria E. Morete; Ana Freitas; Marcia H. Engel; Richard M. Pace; Phillip J. Clapham (Marine Mammal Science, 2003)
A bstract We describe a novel behavior, termed “tail‐up,” observed in humpback whales ( Megaptera novaeangliae ) on wintering grounds on Abrolhos Bank, Brazil. The behavior involves the whale positioned vertically in the water column with its tail in the air. With the exception of calves, tail‐up was observed in all social classes, and its frequency increased through the end of the season. Tail‐ups were recorded in 144 (5.8%) of 2,465 groups of whales observed from a shore station, and in 297 (14.9%) of 1,996 groups observed from vessel surveys; biases in each method suggest that the true frequency lies between these sources. One hundred and fifty‐two hours of continuous sampling showed that the dutation of tail‐up events lasted from a few seconds to 12 min and was longest in groups comprised of a single adult. The maximum duration of a recorded period that consistently included tail‐up was 10 h; however, some individuals were observed to engage in the behavior at night and for four consecutive days. Tail‐up movement speed did not vary by social class; however, it varied according to wind direction and speed. The characteristics of tail‐up that we observed showed that it differed from the descriptions of similar behaviors in other cetacean species. The function of tail‐up is unknown, but we suggest that it may be a multifunctional behavior.

Influence of Mistletoe ( Viscum album ) Extracts on Phagocytosis/Burst Activity of Human Phagocytes - U. Frank; I. Engels; A. Wagner; M. Lacour; F. D. Daschner (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Potential for Retroposition by Old Alu Subfamilies - Karla Johanning; Claudina Alemn Stevenson; Oluwatosin O. Oyeniran; Yair M. Gozal; Astrid M. Roy-Engel; Jerzy Jurka; Prescott L. Deininger (Journal of Molecular Evolution, 2003)

Verotoxin sensitivity of ECV304 cells in vitro and in vivo in a xenograft tumour model: VT1 as a tumour neovascular marker - Hannah M. Heath-Engel; Clifford A. Lingwood (Angiogenesis, 2003)

Alanine dehydrogenase from the psychrophilic bacterium strain PA-43: overexpression, molecular characterization, and sequence analysis - Jane A. Irwin; Susan V. Lynch; Suzie Coughlan; Patrick J. Baker; Haflidi M. Gudmundsson; Gudni A. Alfredsson; David W. Rice; Paul C. Engel (Extremophiles, 2003)

The giant B chromosome of the cyprinid fish Alburnus alburnus harbours a retrotransposon-derived repetitive DNA sequence - C. G. Ziegler; D. K. Lamatsch; C. Steinlein; W. Engel; M. Schartl; M. Schmid (Chromosome Research, 2003)

Latency and reactivation of bovine herpesvirus 1 (BHV-1) in goats and of caprine herpesvirus 1 (CapHV-1) in calves - A. Six; M. Banks; M. Engels; C. Ros Bascuñana; M. Ackermann (Archives of Virology, 2001)

Transcriptional analysis of the gene for glutamine synthetase II and two upstream genes in Streptomyces coelicolor A3(2) - N. Weißschuh; D. Fink; S. Vierling; M. J. Bibb; W. Wohlleben; A. Engels (Molecular Genetics and Genomics, 2000)

Glycoprotein C of bovine herpesvirus 5 (BHV-5) confers a distinct heparin-binding phenotype to BHV-1 - A. Liman; M. Engels; G. Meyer; M. Ackermann (Archives of Virology, 2000)

Restriction endonuclease analysis of the genome of two Italian caprine herpesvirus 1 strains - A. Pratelli; G. Greco; P. Dall'Ara; M. Engels; M. Tempesta; C. Buonavoglia (Archives of Virology, 2000)

Comparison of several approaches of therapeutic drug monitoring of cyclosporin A based on individual pharmacokinetics - R. Wacke; B. Rohde; G. Engel; G. Kundt; E. -M. Hehl; R. Bast; H. Seiter; B. Drewelow (European Journal of Clinical Pharmacology, 2000)

Combined analysis of field and model data: A case study of the phosphate dynamics in the German Bight in summer 1994 - Th. Pohlmann; Th. Raabe; R. Doerffer; S. Beddig; U. Brockmann; S. Dick; M. Engel; K. -J. Hesse; P. König; B. Mayer; A. Moll; D. Murphy; et al. (Ocean Dynamics, 1999)

5-HT 3 receptor over-expression enhances ethanol sensitivity in mice - S. R. Engel; A. M. Allan (Psychopharmacology, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Characterization of microsatellite markers in the red alga Gracilaria gracilis - H Luo; M Möorchen; C. R Engel; C Destombe; J. T Epplen; C Epplen; P Saumitou‐Laprade; M Valero (Molecular Ecology, 1999)

Caddisflies (Trichoptera: Hydropsychidae) Used for Evaluating Water Quality of Large European Rivers - S. C. Stuijfzand; S. Engels; E. van Ammelrooy; M. Jonker (Archives of Environmental Contamination and Toxicology, 1999)

Involvement of the medial geniculate body in prepulse inhibition of acoustic startle - Jianhua Zhang; Jörgen A. Engel; M. Ericson; L. Svensson (Psychopharmacology, 1999)

Increased allocation to external hyphae of arbuscular mycorrhizal fungi under CO 2 enrichment - I. R. Sanders; R. Streitwolf-Engel; M. G. A. van der Heijden; T. Boller; A. Wiemken (Oecologia, 1998)

5-HT 3 receptor over-expression decreases ethanol self administration in transgenic mice - S. R. Engel; C. R. Lyons; A. M. Allan (Psychopharmacology, 1998)

Short allele dominance as a source of heterozygote deficiency at microsatellite loci: experimental evidence at the dinucleotide locus Gv1CT in Gracilaria gracilis (Rhodophyta) - R. WATTIER; C. R. ENGEL; P. SAUMITOU‐LAPRADE; M. VALERO (Molecular Ecology, 1998)
In this study, we compared the genotypes obtained at a microsatellite locus using two methods of amplification and detection of variation in a set of individuals belonging to the red alga haplo‐diploid species, Gracilaria gracilis . The methods varied in their capacity to detect longer alleles in heterozygotes, resulting in an apparent heterozygote deficiency. We attributed this bias in favour of short alleles to competition leading to the preferential amplification of shorter alleles (short allele dominance). To test this hypothesis, we created artificial heterozygotes (mixtures of two haploid DNA samples) and showed that long alleles already less intense than short alleles, ‘suffer’ more from being in association.

Poor correlation between microimmunofluorescence serology and polymerase chain reaction for detection of vascular Chlamydia pneumoniae infection in coronary artery disease patients - M. Maass; Jens Gieffers; Eike Krause; Peter M. Engel; Claus Bartels; Werner Solbach (Medical Microbiology and Immunology, 1998)

Confocal laser scanning microscopy of tumor/vessel relationship in xenografts in nude and scid mice - J. Rygaard; A. -M. Engel; M. Bæksted (Folia Microbiologica, 1998)

Immune selection in murine tumors. A study of MCA induced sarcomas in normal and immunodeficient mice - A. -M. Engel; I. M. Svane; J. Rygaard; O. Werdelin (Folia Microbiologica, 1998)

α and β glucocorticoid receptor mRNA expressionin skeletal muscle - Solange H. Korn; Esther Koerts-De Lang; Guido E. J. Engel; Jan-Willem Arends; Emiel F. M. Wouters; Frederik B. J. M. Thunnissen (Journal of Muscle Research and Cell Motility, 1998)

Studies on the attractional effect of root exudates on hyphal growth of an arbuscular mycorrhizal fungus in a soil compartment-membrane system - H. Vierheilig; M. Alt-Hug; R. Engel-Streitwolf; P. Mäder; A. Wiemken (Plant and Soil, 1998)

Fluoromethylhistidine inhibits tumor growth without producing depletion of endogenous histamine - G. Cricco; N. Engel; M. Croci; C. Davio; G. Martín; C. Fitzsimons; R. Bergoc; E. Rivera (Inflammation Research, 1997)

Mast cell-mediated induction of ICAM-1, VCAM-1 and E-selectin in endothelial cells in vitro: constitutive release of inducing mediators but no effect of degranulation - Charles M. C. J. van Haaster; Josien G. Derhaag; W. Engels; Paul J. M. R. Lemmens; Annemie P. Gijsen; Gerard Hornstra; Ger J. van der Vusse; Adrian M. Duijvestijn (Pflügers Archiv - European Journal of Physiology, 1997)

(−)Alprenolol potentiates the disrupting effects of dizocilpine on sensorimotor function in the rat - Jianhua Zhang; Jörgen A. Engel; David M. Jackson; Christina Johansson; L. Svensson (Psychopharmacology, 1997)

Analysis of structural and numerical chromosome abnormalities in sperm of normal men and carriers of constitutional chromosome aberrations. A review - Martina Guttenbach; Wolfgang Engel; M. Schmid (Human Genetics, 1997)

Dietary modulation of fatty acid composition of mast cell phospholipids does not affect histamine release induced by compound 48/80 - W. Engels; C. M. C. J. Van Haaster; P. J. M. R. Lemmens; G. J. Van der Vusse; G. Hornstra (Inflammation Research, 1997)

Segregation of sex chromosomes into sperm nuclei in a man with 47,XXY Klinefelter's karyotype: a FISH analysis - M. Guttenbach; H. W. Michelmann; B. Hinney; W. Engel; M. Schmid (Human Genetics, 1997)

Antigen-evoked mast cell degranulation in the isolated rat heart: No effect on subsequent ischemia-reperfusion induced damage - W. Engels; C. M. C. J. Van Haaster; W. Vleeming; G. J. Van der Vusse (Inflammation Research, 1997)

Anticipatory and sequential motor control in piano playing - K. C. Engel; M. Flanders; J. F. Soechting (Experimental Brain Research, 1997)

Detection of toxic phytoplankton species by immunochemical particle analysis based on flow cytometry - Engel G. Vrieling; Winfried W. C. Gieskes; Wilhelmus J. M. Zeijl; Marten Veenhuis (Aquatic Ecology, 1994)

Reversible interconversion of the functional state of the gene regulator FNR from Escherichia coli in vivo by O2 and iron availability - P. Engel; M. Trageser; G. Unden (Archives of Microbiology, 1991)

Bovine herpesvirus 1: Molecular and antigenic characteristics of variant viruses isolated from calves with neurological disease - A. E. Metzler; A. A. Schudel; M. Engels (Archives of Virology, 1986)

Opsonization and phagocytosis ofPseudomonas aeruginosa: The inhibitory role of lipopolysaccharide - W. Engels; J. Endert; M. Kamps; C. P. A. Van Boven (Antonie van Leeuwenhoek, 1985)

European isolates of bovine herpesvirus 1: A comparison of restriction endonuclease sites, polypeptides, and reactivity with monoclonal antibodies - A. E. Metzler; H. Matile; U. Gassmann; M. Engels; R. Wyler (Archives of Virology, 1985)

Demonstration of an IgG-Fc receptor in ratcytomegalovirus infected cells - C. A. Bruggeman; R. Reinders; W. M. H. Debie; P. M. Frederik; W. Engels; C. P. A. van Boven (Archives of Virology, 1984)

The nature of the competitive ability of spontaneous staphylocoagulase-negative mutants of Staphylococcus aureus with respect to growth of the parent strains in continuous culture - W. Engels; M. A. F. Kamps (Antonie van Leeuwenhoek, 1982)

Secretion of staphylocoagulase by Staphylococcus aureus: the role of a cell-bound intermediate - W. Engels; M. A. F. Kamps (Antonie van Leeuwenhoek, 1981)

The competitive ability of spontaneous staphylocoagulase-negative mutants of Staphylococcus aureus 104 and NCTC 8178 towards the parent strains in continuous culture - W. Engels; M. Kamps (Antonie van Leeuwenhoek, 1981)

Continuous culture studies on the production of staphylocoagulase by Staphylococcus aureus - W. Engels; M. A. F. Kamps; C. P. A. van Boven (Antonie van Leeuwenhoek, 1980)

Gene action in fish of tetraploid origin. IV. Ribosomal DNA amount in clupeoid and salmonoid fish - J. Schmidtke; M. T. Zenzes; C. Weiler; K. Bross; W. Engel (Biochemical Genetics, 1976)

Photoinaktivierung von Nitrobacter winogradskyi Buch - Mariegret Mller-Neuglck; Horst Engel (Archives of Microbiology, 1961)

Untersuchungen ber die bakterielle Schwefeloxydation in der Elbe - Bernhard Mtze; Horst Engel (Archives of Microbiology, 1960)